Continuous fiber reinforced resin molded body and method for producing the same
By optimizing the interface compatibility and molding sealing of fibers and resins, the problem of low interface adhesion between fibers and resins in the prior art is solved, and a continuous fiber-reinforced resin molded body with high strength, rigidity and impact strength is realized.
Patent Information
- Application Number
- CN202111628278.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-11-30
- Filing Date
- 2019-04-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2039-04-23
AI Technical Summary
The continuous fiber-reinforced resin molded body in the prior art has low adhesion and affinity at the extreme interface between the fiber and the resin, resulting in a large number of voids and unable to exhibit sufficient strength and impact absorption properties.
By optimizing the compatibility of the coated adhesive agent applied in the manufacturing of continuous reinforcement fibers with resin and the sealing properties in molding, reducing voids in the extreme interface, the press molding method is used to produce a continuous fiber reinforced resin molded body with high strength and rigidity.
The high strength, rigidity, impact strength and long-term characteristics of the continuous fiber-reinforced resin molded body are realized, the loss tangent and energy storage modulus are reduced, and the impregnation of the resin is improved.
Smart Images

Figure CN114106369B_ABST
Abstract
Description
[0001] This application is a divisional application. The international application number of the original application is PCT / JP2019 / 017285, the international application date is April 23, 2019, the Chinese national application number is 201980013489.7, the date of entry into China is August 14, 2020, and the name of the invention is "Continuous fiber reinforced resin molded body and its manufacturing method". Technical Field
[0002] The present invention relates to a continuous fiber reinforced resin molded body and a method for producing the same. More specifically, the present invention relates to: a continuous fiber reinforced resin molded body having high adhesion and affinity at the interface between continuous reinforcing fibers and synthetic resin, having few voids in the interface, and being able to exhibit sufficient strength; a continuous fiber reinforced resin molded body having sufficiently small loss tangent and being able to exhibit sufficient impact absorption; a continuous fiber reinforced resin molded body having sufficiently large storage modulus and being able to exhibit sufficient impact strength; a continuous fiber reinforced resin molded body having high resin impregnation, high strength and rigidity; and methods for producing the same. Background Art
[0003] Composite molded bodies formed by adding reinforcing materials such as glass fibers to matrix resin materials are used in structural parts of various machines or automobiles, pressure vessels, and tubular structures. In particular, from the perspective of strength, the reinforcing fibers are continuous fibers, and from the perspective of molding cycle and recyclability, continuous fiber reinforced resin molded bodies in which the resin is a thermoplastic resin are preferred. As such continuous fiber reinforced resin molded bodies, the following schemes have been proposed: a scheme for studying a sizing agent added to the reinforcing fibers (for example, see the following patent document 1); a scheme for studying the difference between the melting temperature (melting point) and the crystallization temperature of the thermoplastic resin (for example, see the following patent document 2); a scheme for adding an organic salt to the resin material (for example, see the following patent document 3); a scheme for laminating a fabric of a molding precursor with a thermoplastic resin (for example, see the following patent document 4); a scheme for improving the impregnation property by first impregnating the reinforcing fibers with a low melting point thermoplastic resin (for example, see the following patent document 5); a scheme for having good resistance to interlayer delamination by using two resins with different melting points in the surface resin (for example, see the following patent document 6).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2003-238213
[0007] Patent Document 2: Japanese Patent No. 5987335
[0008] Patent Document 3: Japanese Patent Application Publication No. 2017-222859
[0009] Patent Document 4: Japanese Patent Application Publication No. 2009-19202
[0010] Patent Document 5: Japanese Patent Application Laid-Open No. 10-138379
[0011] Patent Document 6: Japanese Patent No. 5878544 Summary of the invention
[0012] Problems to be solved by the invention
[0013] However, the inventors have conducted in-depth research and found that in the conventional continuous fiber reinforced resin molded bodies, the interface adhesion and affinity between the glass fiber and the matrix resin in any of the continuous reinforcing fibers are very low, so there are many voids in the polar interface area between the fiber and the resin, and sufficient strength cannot be exhibited, and the performance is not suitable for parts requiring high strength. In addition, in the conventional continuous fiber reinforced resin molded bodies, since the loss tangent of any molded body is very high, sufficient impact absorption cannot be exhibited, and the performance is not suitable for parts requiring high impact absorption; since the storage modulus of any molded body is very low, sufficient impact strength cannot be exhibited, and the performance is not suitable for parts requiring high impact strength; the resin impregnation in the continuous reinforcing fibers is low, so the bonding between the resin and the continuous reinforcing fibers is insufficient, and the physical properties such as strength and rigidity and productivity are poor.
[0014] In view of the level of the prior art, the problem to be solved by the present invention is to provide: a continuous fiber reinforced resin molded body having high adhesion and affinity at the polar interface between the continuous reinforcing fibers and the synthetic resin, with few voids in the polar interface and capable of exhibiting sufficient strength; a continuous fiber reinforced resin molded body having a low loss tangent and capable of exhibiting sufficient impact strength; a continuous fiber reinforced resin molded body having a high storage modulus and capable of exhibiting sufficient impact strength; and a continuous fiber reinforced resin molded body having high resin impregnation, high strength and rigidity; and methods for manufacturing them.
[0015] Means for solving problems
[0016] The inventors of the present invention have conducted in-depth research and repeated experiments to solve this problem, and unexpectedly found that by taking measures for the compatibility of the sizing agent (also called a sizing agent) applied in the manufacture of continuous reinforcing fibers with the resin, the airtightness during molding, the flow of the resin, etc., there are very few voids at the polar interface between the continuous reinforcing fibers and the synthetic resin, thereby a continuous fiber-reinforced resin molded body with high strength and rigidity can be manufactured by using its press molding; and the loss tangent of the continuous fiber-reinforced resin molded body is reduced, and a continuous fiber-reinforced resin molded body with high impact absorption can be manufactured by using its press molding; the storage modulus of the continuous fiber-reinforced resin molded body is increased, and a continuous fiber-reinforced resin molded body with high impact strength can be manufactured by using its press molding; in a continuous fiber-reinforced resin molded body having two or more thermoplastic resins, the ratio of each resin in the polar interface region between the continuous reinforcing fibers and the resin is different from the ratio of each resin in other resin regions, thereby making the continuous fiber-reinforced resin molded body exhibit high strength and rigidity, thereby completing the present invention.
[0017] That is, the present invention is as follows.
[0018] [1] A continuous fiber reinforced resin molded body comprising continuous reinforcing fibers having a substantially circular cross-section and a synthetic resin, wherein at an interface between one of the continuous reinforcing fibers and the synthetic resin in a cross section perpendicular to the longitudinal direction of the continuous reinforcing fibers, the number of continuous reinforcing fibers having a porosity of 10% or less in a peripheral outer region that is one-tenth of the radius of one of the continuous reinforcing fibers from the peripheral portion of the continuous reinforcing fibers is at least 10% of the total number of the continuous reinforcing fibers.
[0019] [2] The continuous fiber-reinforced resin molded product as described in [1] above, wherein the number of continuous reinforcing fibers having a porosity of 10% or less accounts for 90% or more of the total number of the continuous reinforcing fibers.
[0020] [3] The continuous fiber-reinforced resin molded product as described in [2] above, wherein the number of continuous reinforcing fibers having a porosity of 1% or less accounts for 90% or more of the total number of the continuous reinforcing fibers.
[0021] [4] The continuous fiber reinforced resin molded product according to any one of [1] to [3] above, wherein the impregnation rate of the synthetic resin in the continuous fiber reinforced resin composite is 99% or more.
[0022] [5] The continuous fiber reinforced resin molded body according to any one of [1] to [4] above, wherein the continuous reinforcing fibers are glass fibers, and the continuous fiber reinforced resin molded body has a tensile stress of 480 MPa or more.
[0023] [6] The continuous fiber reinforced resin molded body according to any one of [1] to [5] above, wherein the continuous reinforcing fibers are glass fibers, and the flexural modulus of the continuous fiber reinforced resin molded body is 22 GPa or more.
[0024] [7] A continuous fiber-reinforced resin molded product comprising a thermoplastic resin and continuous reinforcing fibers, wherein the loss tangent in a torsional mode is 0.11 or less.
[0025] [8] The continuous fiber-reinforced resin molded product as described in [7] above, wherein the peak temperature of the loss tangent is 78° C. or higher.
[0026] [9] A continuous fiber reinforced resin molded body comprising continuous reinforcing fibers and a thermoplastic resin, wherein the storage modulus in a torsional mode is 3.4 GPa or more.
[0027]
[10] The continuous fiber reinforced resin molded body as described in [9] above, wherein the storage modulus when cut in an oblique direction is 1.5 times or more the storage modulus when cut in a straight direction.
[0028]
[11] The continuous fiber-reinforced resin molded product as described in [9] or
[10] above, wherein the storage modulus at 150°C is 25% or more of the maximum storage modulus.
[0029]
[12] The continuous fiber-reinforced resin molded article according to any one of [9] to
[11] above, wherein the shear viscosity is 330 MPa·s -1 above.
[0030]
[13] A continuous fiber reinforced resin molded body comprising continuous reinforcing fibers and a thermoplastic resin, wherein the flexural storage modulus is 22 GPa or more.
[0031]
[14] The continuous fiber-reinforced resin molded product as described in
[13] above, wherein the flexural storage modulus at 150°C is 76% or more of the storage modulus at 30°C.
[0032]
[15] The continuous fiber-reinforced resin molded product as described in
[13] or
[14] above, wherein the flexural storage modulus retention rate during oblique cutting is 58% or more.
[0033]
[16] The continuous fiber-reinforced resin molded product according to any one of
[13] to
[15] above, wherein the tensile storage modulus at 50°C is 22 GPa or more.
[0034]
[17] The continuous fiber-reinforced resin molded product as described in any one of
[13] to
[16] above, wherein the maximum value of the tensile loss tangent is 0.037 or less.
[0035]
[18] The continuous fiber-reinforced resin molded product according to any one of
[13] to
[17] above, wherein the temperature at which the tensile storage modulus and the flexural storage modulus are reversed is 95° C. or higher.
[0036]
[19] The continuous fiber reinforced resin molded body as described in any one of
[13] to
[18] above, wherein {(tensile storage modulus - flexural storage modulus) at 30°C} / {(flexural storage modulus - tensile storage modulus) at 200°C}≧1.
[0037]
[20] A continuous fiber reinforced resin molded body comprising continuous reinforcing fibers having a substantially circular cross-section and two or more thermoplastic resins, characterized in that, at an interface between one of the continuous reinforcing fibers and the thermoplastic resin in a cross section perpendicular to the longitudinal direction of the continuous reinforcing fibers, in a peripheral outer region that is one-tenth of the radius of one of the two or more continuous reinforcing fibers away from the peripheral portion of the continuous reinforcing fibers, the proportion of resins other than the resin having the highest proportion in the entire resin region among the two or more thermoplastic resins is higher than the proportion of the resin having the highest proportion in the entire resin region, and in a resin region outside the peripheral outer region, resins other than the resin having the highest proportion in the entire resin region among the two or more thermoplastic resins are uniformly dispersed or mixed.
[0038]
[21] The continuous fiber-reinforced resin molded product as described in
[20] above, wherein the two or more thermoplastic resins have a sea-island structure.
[0039]
[22] A continuous fiber reinforced resin molded body as described in
[20] or
[21] above, wherein the difference between the melting points of the resin with the highest melting point and the resin with the lowest melting point among the two or more thermoplastic resins is 100°C or more.
[0040]
[23] A continuous fiber reinforced resin molded body as described in any one of
[20] to
[22] above, wherein the melting point of the mixture of the above two or more thermoplastic resins is substantially the same as the melting point of the resin with the highest proportion in the overall resin region among the above two or more thermoplastic resins.
[0041]
[24] A continuous fiber reinforced resin molded body as described in any one of
[20] to
[23] above, wherein the difference between the heating melting peak temperature and the cooling crystallization peak temperature of the mixture of the above two or more thermoplastic resins is smaller than the difference between the heating melting peak temperature and the cooling crystallization peak temperature of the resin with the highest proportion in the overall resin region among the above two or more thermoplastic resins.
[0042]
[25] A continuous fiber reinforced resin molded body as described in any one of
[20] to
[24] above, wherein the bonding force between at least one resin other than the resin with the highest proportion in the overall resin region among the above two or more thermoplastic resins and the above continuous reinforcing fibers is greater than the bonding force between the resin with the highest proportion in the overall resin region and the above continuous reinforcing fibers.
[0043]
[26] A continuous fiber reinforced resin molded body as described in any one of
[20] to
[25] above, wherein the difference in surface tension between at least one resin other than the resin with the highest proportion in the overall resin region among the above two or more thermoplastic resins and the above continuous reinforcing fibers is smaller than the difference in surface tension between the resin with the highest proportion in the overall resin region and the above continuous reinforcing fibers.
[0044]
[27] A continuous fiber reinforced resin molded body as described in any one of
[20] to
[26] above, wherein among the two or more thermoplastic resins, at least one resin other than the resin with the highest proportion in the entire resin region has higher wettability with respect to the continuous reinforcing fibers than the resin with the highest proportion in the entire resin region.
[0045]
[28] A method for manufacturing a continuous fiber reinforced resin composite material, comprising the following steps:
[0046] A step of heating and pressing a continuous reinforcing fiber to which a sizing agent including a coupling agent, a bundling agent and a lubricant is added and a thermoplastic resin having a terminal functional group reactive with the coupling agent so as to reach a temperature not lower than the melting point of the thermoplastic resin; and
[0047] This is cooled to a temperature below the melting point of the thermoplastic resin to obtain a continuous fiber reinforced resin composite material as a molded product.
[0048]
[29] The method according to
[28] above, wherein the water absorption rate of the thermoplastic resin is 0.1 wt% or more.
[0049]
[30] The method as described in
[28] or
[29] above, wherein 50% by weight or more of the sizing agent is diffused into the thermoplastic resin during the heating and pressing process.
[0050]
[31] The method according to any one of
[28] to
[30] above, wherein the coupling agent is bonded to a terminal functional group of the thermoplastic resin.
[0051]
[32] The method as described in any one of
[28] to
[31] above, wherein the amount of terminal functional groups in the continuous fiber reinforced resin composite material is less than the amount of terminal functional groups contained in the thermoplastic resin.
[0052]
[33] The method according to any one of
[28] to
[32] above, wherein the amount of the terminal functional groups is 90% or less of the amount of the terminal functional groups contained in the thermoplastic resin.
[0053]
[34] The method according to any one of
[28] to
[33] above, wherein the content of the particulate additive contained in the thermoplastic resin is 30 ppm or less.
[0054]
[35] The method as described in any one of
[28] to
[34] above, wherein the thermoplastic resin is a polyamide resin, and the amount of carboxyl terminals contained in the polyamide resin as terminal functional groups reactive with the coupling agent is 65 μmol / g or more.
[0055]
[36] The method as described in any one of
[28] to
[35] above, wherein the thermoplastic resin is a polyamide resin, and the amount of amino terminal contained in the polyamide resin as a terminal functional group reactive with the coupling agent is 40 μmol / g or less.
[0056]
[37] A method for producing a shaped body of a continuous fiber reinforced resin composite material, comprising the following steps: heating the continuous fiber reinforced resin composite material produced by the method described in any one of
[28] to
[36] to a temperature above the melting point of the thermoplastic resin, pressing it using a mold, and then cooling it to a temperature below the melting point of the thermoplastic resin to carry out shaping.
[0057]
[38] The method as described in
[37] above, wherein compression is performed during cooling.
[0058]
[39] A method for producing a fiber-reinforced resin molded body, comprising the following steps: a step of heating and pressing reinforcing fibers and a thermoplastic resin having a droplet generation coefficient with the reinforcing fibers of 10 or more in a manner to a temperature above the melting point of the thermoplastic resin; and a step of cooling the thermoplastic resin to a temperature below the crystallization temperature of the thermoplastic resin.
[0059]
[40] A fiber-reinforced resin molded body comprising glass fiber and polyamide resin, wherein the fiber-reinforced resin molded body is cut and a 400 g / cm 2When the glass fiber is ground with a force and the ground surface is observed by SEM, at the polar interface between one glass fiber and the polyamide resin in a cross section perpendicular to the length direction of the glass fiber, the number of glass fibers with a porosity of less than 10% in the peripheral outer area at a distance from the peripheral part of the glass fiber that is one tenth of the radius of one glass fiber is more than 90% of the total number of glass fibers.
[0060]
[41] The continuous fiber reinforced resin molded product as described in
[40] above, wherein the glass fibers are continuous fibers.
[0061]
[42] A communication device housing, which is a communication device housing formed of a composite material molded product containing a thermoplastic resin and continuous glass-reinforced fibers, characterized in that:
[0062] The tensile strength satisfies the following formula (3):
[0063] Tensile strength in the length direction (MPa) × 0.5 + tensile strength in the width direction (MPa) × 0.5 > 500MPa Formula (3)
[0064] The bending modulus satisfies the following relationship (4):
[0065] Bending modulus in length direction (MPa) × 0.5 + Bending modulus in width direction (MPa) × 0.5 > 30MPa Formula (4)
[0066] Furthermore, the electric field shielding property measured by the KEC method was 10 dB or less in a frequency band of 1 GHz.
[0067]
[43] A continuous fiber reinforced resin molded body comprising continuous reinforcing fibers and a thermoplastic resin, wherein the strength of a fracture due to interlaminar delamination measured by an acoustic emission method is 40 MPa or more.
[0068] Effects of the Invention
[0069] In the continuous fiber reinforced resin molded body of the present invention, the adhesion and affinity at the interface between the continuous reinforcing fibers and the synthetic resin are high, and there are few voids in the interface, which can exhibit sufficient strength, rigidity, impact strength, and high long-term characteristics; and the loss tangent is sufficiently small, which can exhibit sufficient impact absorption; the storage modulus is sufficiently large, which can exhibit sufficient impact strength; the resin resin impregnation is high, which can exhibit high strength and rigidity. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1This is a diagram for explaining the "voids" and "void ratio" existing in the peripheral outer region (polar interface region) which is one tenth of the radius of one continuous reinforcing fiber from the peripheral portion of the continuous reinforcing fiber at the polar interface between one continuous reinforcing fiber and the synthetic resin in a cross section perpendicular to the longitudinal direction of the continuous reinforcing fiber.
[0071] Figure 2 These are photographs of the polar interface regions of Example 1-1, Example 2-1, Example 3-1, and Example 4-1.
[0072] Figure 3 is a photograph of the polar interface region of Examples 1-3.
[0073] Figure 4 This is a photograph of the polar interface region of Comparative Example 1-2.
[0074] Figure 5 This is a photograph of the polar interface region of Comparative Example 1-3.
[0075] Figure 6 This is a photograph in place of a drawing for explaining the synthetic resin "impregnation rate" of a continuous fiber-reinforced resin molded body.
[0076] Figure 7 This is a photograph in lieu of a drawing showing a state in which, at a polar interface between one continuous reinforcing fiber and a synthetic resin in a cross section along the longitudinal direction of a continuous reinforcing fiber having a substantially circular cross section, in a peripheral outer region which is one-tenth of the radius of one continuous reinforcing fiber away from a peripheral portion of the continuous reinforcing fiber, the proportion of a resin other than the resin having the highest proportion in the entire resin region among two or more thermoplastic resins is higher than the proportion of the resin having the highest proportion in the entire resin region, and in a resin region outside the peripheral outer region, the resin other than the resin having the highest proportion in the entire resin region among the two or more thermoplastic resins is uniformly dispersed.
[0077] Figure 8 This is a photograph of the polar interface region of Example 6-1.
[0078] Fig. 9 This is a photograph of the polar interface region of Comparative Example 6-2.
[0079] Fig.10 This is a photograph of the polar interface region of Example 10.
[0080] Fig.11 This is a photograph of the polar interface region of Comparative Example 10.
[0081] Fig.12 The figure shows the shape of the smartphone casing of Example 9. DETAILED DESCRIPTION
[0082] The embodiments of the present invention are described in detail below.
[0083] [Continuous fiber reinforced resin molded body]
[0084] The continuous fiber reinforced resin molded body of the present embodiment is a continuous fiber reinforced resin molded body containing continuous reinforcing fibers of a substantially circular cross-section and a synthetic resin, wherein at the polar interface between one of the continuous reinforcing fibers and the synthetic resin in a cross section orthogonal to the longitudinal direction of the continuous reinforcing fibers, the number of continuous reinforcing fibers having a porosity of 10% or less in a peripheral outer region that is one-tenth of the radius of one of the continuous reinforcing fibers from the peripheral portion of the continuous reinforcing fibers is 10% or more of the total number of the continuous reinforcing fibers; and preferably, the loss tangent (tanδ) in the torsion mode in the dynamic viscoelasticity measurement is 0.11 or less; the storage modulus in the torsion mode in the dynamic viscoelasticity measurement is 3.4 GPa or more; and the storage modulus in the bending mode is 22 GPa or more. Furthermore, when two or more thermoplastic resins are used, it is preferred that, at the polar interface between one of the continuous reinforcing fibers and the thermoplastic resin in a cross section perpendicular to the longitudinal direction of the continuous reinforcing fibers, in a peripheral outer region (also referred to as a polar interface region) which is one-tenth of the radius of one of the continuous reinforcing fibers from the peripheral portion of the continuous reinforcing fibers, the proportion of a resin (also referred to as a secondary resin) other than the resin having the highest proportion in the entire resin region among the two or more thermoplastic resins is higher than the proportion of the resin having the highest proportion in the entire resin region, and in a resin region (also referred to as an other resin region) other than the peripheral outer region, the resin (secondary resin) other than the resin having the highest proportion in the entire resin region among the two or more thermoplastic resins is uniformly dispersed or mixed.
[0085] In addition, the method for producing the continuous fiber-reinforced resin composite material according to the present embodiment preferably includes the following steps:
[0086] A step of heating and pressing a continuous reinforcing fiber to which a sizing agent including a coupling agent, a bundling agent and a lubricant is added and a thermoplastic resin having a terminal functional group reactive with the coupling agent so as to reach a temperature not lower than the melting point of the thermoplastic resin; and
[0087] This is cooled to a temperature below the melting point of the thermoplastic resin to obtain a continuous fiber reinforced resin composite material as a molded product.
[0088] That is, Figure 1As shown, the continuous fiber reinforced resin molded body of the present embodiment is a continuous fiber reinforced resin molded body containing continuous reinforcing fibers of approximately circular cross-section and synthetic resin, wherein the following continuous reinforcing fibers are present: the porosity in the peripheral outer region (also referred to as the polar interface region) observed at the polar interface between one of the continuous reinforcing fibers and the synthetic resin in a cross section perpendicular to the length direction of the continuous reinforcing fibers and at a radial distance from the peripheral portion of the continuous reinforcing fibers by one tenth of the radius r of one of the continuous reinforcing fibers (i.e., r / 10) is 10% or less, and the number of such continuous reinforcing fibers is more than 10% of the total number of continuous reinforcing fibers. It should be noted that the cross section of the continuous reinforcing fibers is preferably a substantially circular cross section, and may also be as follows Figure 1 The ellipse is shown. In this case, the "radius" refers to the shortest distance from the center of the fiber cross section to the periphery.
[0089] In the continuous fiber reinforced resin molded body of the present embodiment, in the polar interface region, the proportion of the secondary resin among the two or more thermoplastic resins is preferably higher than the proportion of the primary resin. Figure 7 .
[0090] The void ratio in "a peripheral outer region of a continuous reinforcing fiber at a distance of one tenth of the radius of one continuous reinforcing fiber from the peripheral portion of the continuous reinforcing fiber observed at the polar interface between one continuous reinforcing fiber and the synthetic resin in a cross section perpendicular to the longitudinal direction of the continuous reinforcing fiber" can be determined, for example, as follows: for a cross section perpendicular to the longitudinal direction of the continuous reinforcing fiber-reinforced resin molded body cut into 1 cm squares by a band saw or the like, a 400 g / cm 2 The grinding table was rotated at 100 rpm in a manner with a force of 100 rpm, and the sample was polished with #220 waterproof sandpaper for 10 minutes, #400 waterproof sandpaper for 2 minutes, #800 waterproof sandpaper for 5 minutes, #1200 waterproof sandpaper for 10 minutes, #2000 waterproof sandpaper for 15 minutes, 9 μm silicon carbide film for 15 minutes, 5 μm aluminum oxide film for 15 minutes, 3 μm aluminum oxide film for 15 minutes, 1 μm aluminum oxide film for 15 minutes, and 0.1 μm colloidal silica (Baikalox 0.1CR) using foamed polyurethane with polishing paper for 10 minutes. During each polishing, water was added at about 7 mL / min while polishing. The polished sample was observed using a scanning electron microscope (SEM), and the image was analyzed using software such as ImageJ, thereby calculating the porosity using the following formula.
[0091] Void ratio (%) = (area of voids in the peripheral region outside the continuous reinforcing fiber that is one-tenth of the radius of the continuous reinforcing fiber) / (area of the peripheral region outside the continuous reinforcing fiber that is one-tenth of the radius of the continuous reinforcing fiber) × 100
[0092] First, the porosity in the peripheral outer region (also referred to as "region of one tenth of the diameter of the continuous reinforcing fiber", "polar interface region") of one arbitrary continuous reinforcing fiber having a substantially circular cross section and one tenth of the radius from the peripheral portion of the continuous reinforcing fiber is obtained, and the porosity is observed for any 100 fibers. In the molded body of the present embodiment, from the perspective of improving the rigidity and strength of the molded body, the number of fibers having a porosity of 10% or less in the region of one tenth of the diameter of the continuous reinforcing fiber is 10 or more out of 100 fibers, that is, 10% or more, preferably 20% or more, more preferably 50% or more, still more preferably 70% or more, and most preferably 90% or more.
[0093] In the molded article of the present embodiment, the porosity of the region of one tenth of the diameter of the continuous reinforcing fibers is preferably 5% or less, more preferably 2% or less, and even more preferably 1% or less, from the viewpoint of improving the rigidity and strength of the molded article.
[0094] In order to make the number of fibers having a void ratio of 10% or less in the region of one-tenth of the diameter of the continuous reinforcing fiber be 10% or more among 100 fibers, for example, when the continuous reinforcing fiber is a glass fiber, it is preferably selected from a material having a droplet generation coefficient of 10 or more and good compatibility between the sizing agent (sizing agent) applied in the manufacture of the glass fiber and the synthetic resin, and a molding method such as a concave mold that can seal the inside of the mold during molding or a molding method using a double-belt press with adjusted pressure is selected, thereby preventing leakage of the resin, reducing the change in the occupied volume (Vf, also called volume content) of the glass fiber in the continuous fiber-reinforced resin molded body before and after molding, and molding is performed under temperature conditions suitable for the sizing agent.
[0095] The loss tangent in the torsion mode can be calculated from the value of the peak of the loss tangent by, for example, cutting the continuous fiber in the 0° and 90° directions with a band saw or the like and measuring the viscoelasticity of the obtained continuous fiber-reinforced resin molded body in the torsion mode under a nitrogen atmosphere and at a constant heating rate. The loss tangent in the torsion mode of the continuous fiber-reinforced resin molded body of the present embodiment is preferably 0.11 or less, preferably 0.10 or less, more preferably 0.095 or less, further preferably 0.090 or less, and most preferably 0.087 or less.
[0096] The temperature at which the continuous fiber-reinforced resin molded product of the present embodiment shows the peak top of the loss tangent in the torsional mode is preferably 78°C or higher, more preferably 80°C or higher, further preferably 82°C or higher, and most preferably 84°C or higher.
[0097] In the continuous fiber reinforced resin molded body of the present embodiment, when the above-mentioned loss tangent is plotted against each temperature, two peaks preferably appear, and the difference between the above-mentioned two peaks is preferably 80°C or less, more preferably 60°C or less, further preferably 50°C or less, and most preferably 35°C or less.
[0098] In order to manufacture the above-mentioned continuous fiber reinforced resin molded body having a loss tangent of 0.11 or less, for example, when the continuous reinforcing fiber is glass fiber, it is preferred to select a material having a droplet generation coefficient of 10 or more and good compatibility between the sizing agent (sizing agent) applied during the manufacture of the glass fiber and the synthetic resin, and select a molding method such as an inner concave mold that can seal the inside of the mold during molding, or a molding method using a double-belt press with adjusted pressure, thereby preventing leakage of the resin, reducing the change in the occupied volume (Vf, also called volume content) of the glass fiber in the continuous fiber reinforced resin molded body before and after molding, and performing molding under temperature conditions suitable for the sizing agent.
[0099] Regarding the storage modulus in the torsion mode, for example, the continuous fiber can be cut along the 0° and 90° directions using a band saw or the like, and the obtained continuous fiber reinforced resin molded body can be subjected to torsion mode viscoelasticity measurement under a nitrogen atmosphere and a constant heating rate, and the storage modulus at each temperature can be plotted, and the storage modulus can be calculated from the value of the peak of the storage modulus at this time. The storage modulus in the torsion mode of the continuous fiber reinforced resin molded body of the present embodiment is preferably 3.4 GPa or more, preferably 3.5 GPa or more, more preferably 4.0 GPa or more, further preferably 4.5 GPa or more, further preferably 6.0 GPa or more, and most preferably 7.0 GPa or more.
[0100] In the continuous fiber reinforced resin molded body of the present embodiment, when the storage modulus is measured using a test piece obtained by cutting the continuous fiber reinforced resin molded body along the 45° direction (inclined direction) of the continuous fiber, the storage modulus is preferably 1.5 times or more of the storage modulus when measured using the test piece obtained by cutting along the 0° and 90° directions, more preferably 1.6 times or more, further preferably 1.7 times or more, and most preferably 1.9 times or more.
[0101] In the continuous fiber-reinforced resin molded product of the present embodiment, the storage modulus at 150° C. is preferably 25% or more of the maximum storage modulus, and more preferably 26% or more.
[0102] In the continuous fiber-reinforced resin molded article of the present embodiment, the shear viscosity in the viscoelasticity measurement in the torsional mode is preferably 330 MPa·s -1 More preferably, 470 MPa·s -1 More preferably, 500 MPa·s -1 Above, most preferably 700 MPa·s -1 above.
[0103] In order to manufacture a continuous fiber reinforced resin molded body with a storage modulus of 3.4 GPa or more in a torsional mode, for example, when the continuous reinforcing fiber is a glass fiber, it is preferred to select a material in which the droplet generation coefficient between the sizing agent (bundling agent) applied in the manufacture of the glass fiber and the synthetic resin is 10 or more and has good compatibility, and a molding method such as an inner concave mold that can seal the inside of the mold during molding or a molding method using a double-belt press with adjusted pressure is selected, thereby preventing leakage of the resin, reducing the change in the occupied volume (Vf, also called volume content) of the glass fiber in the continuous fiber reinforced resin molded body before and after molding, and molding is performed under temperature conditions suitable for the sizing agent.
[0104] Regarding the bending storage modulus, for example, the continuous fiber can be cut along the 0° and 90° directions using a band saw or the like, and the obtained continuous fiber reinforced resin molded body can be subjected to a bending mode viscoelasticity measurement under a nitrogen atmosphere and a constant heating rate, and the storage modulus at each temperature can be plotted, and the bending storage modulus can be calculated from the maximum storage modulus at that time. The bending storage modulus of the continuous fiber reinforced resin molded body of the present embodiment is preferably 22 GPa or more, preferably 23 GPa or more, more preferably 25 GPa or more, further preferably 31 GPa or more, and most preferably 36 GPa or more.
[0105] In the continuous fiber-reinforced resin molded product of the present embodiment, it is preferred that the flexural storage modulus when the flexural storage modulus is measured at 150°C is 76% or more of the flexural storage modulus at 30°C.
[0106] In the continuous fiber reinforced resin molded body of the present embodiment, when the bending storage modulus is measured using a test piece obtained by cutting the continuous fiber reinforced resin molded body along the 45° direction (inclined direction) of the continuous fiber, the bending storage modulus is preferably 58% or more of the storage modulus when measured using the test piece obtained by cutting along the 0° and 90° directions, more preferably 60% or more, and further preferably 62% or more.
[0107] The tensile storage modulus and tensile loss tangent can be obtained, for example, by measuring the viscoelasticity of the continuous fiber reinforced resin molded body obtained by cutting the continuous fiber along the 0° and 90° directions using a band saw or the like in a nitrogen atmosphere under the condition of a constant heating rate. In the continuous fiber reinforced resin molded body of the present embodiment, the tensile storage modulus at 50°C is preferably 22 GPa or more, more preferably 25 GPa or more, further preferably 30 GPa or more, further preferably 32 GPa or more, further preferably 35 GPa or more, and most preferably 40 GPa or more.
[0108] The maximum tensile loss tangent can be obtained from the maximum point obtained by plotting the loss tangent at each temperature obtained by the above measurement. In the continuous fiber reinforced resin molded body of this embodiment, the maximum loss tangent is preferably 0.037 or less, more preferably 0.035 or less, and further preferably 0.032 or less.
[0109] In the continuous fiber reinforced resin molded body of the present embodiment, when the tensile storage modulus and the flexural storage modulus are plotted against each temperature, the temperature at which the values of the tensile storage modulus and the flexural storage modulus are reversed is preferably 95°C or higher, more preferably 100°C or higher, and further preferably 105°C or higher.
[0110] In the continuous fiber-reinforced resin molded product of the present embodiment, when the tensile storage modulus and the flexural storage modulus are plotted against each temperature, the following formula is preferably satisfied.
[0111] {(tensile storage modulus - flexural storage modulus) at 30°C} / {(flexural storage modulus - tensile storage modulus) at 200°C}≧1
[0112] In order to manufacture a continuous fiber reinforced resin molded body with a flexural storage modulus of 22 GPa or more, for example, when the continuous reinforcing fiber is a glass fiber, it is preferred to select a material in which the droplet generation coefficient between the sizing agent (sizing agent) applied in the manufacture of the glass fiber and the synthetic resin is 10 or more and the compatibility is good, and a molding method such as an inner concave mold that can seal the mold during molding to suppress the flow of the resin or a molding method using a double-belt press with adjusted pressure is selected, thereby preventing leakage of the resin, reducing the change in the occupied volume (Vf, also called volume content) of the glass fiber in the continuous fiber reinforced resin molded body before and after molding, and molding is performed while forming a good interface under temperature conditions suitable for the sizing agent.
[0113] The occupancy ratio (area ratio) of each thermoplastic resin in the above-mentioned peripheral outer region in the continuous fiber reinforced resin molded body of the present embodiment can be calculated, for example, as follows: a cross section in the thickness direction of the continuous fiber reinforced resin molded body (a cross section orthogonal to the length direction of the continuous reinforcing fibers) is cut, embedded in epoxy resin, and carefully ground in a manner that the continuous reinforcing fibers are not damaged, and then an image of the cross section is captured using a laser Raman microscope, and the type of resin contained in the fiber reinforced resin is determined from the obtained image and spectrum, and the respective areas are calculated by image processing based on ImageJ.
[0114] In addition, regarding the distribution of the thermoplastic resin in the resin region other than the polar interface region in the fiber-reinforced resin molded body, for example, a cross section of the continuous fiber-reinforced resin molded body cut along a thickness direction cross section (a cross section orthogonal to the length direction of the continuous reinforcing fibers) can be obtained by applying a 125 g / cm 2 The force is sequentially ground with 220 waterproof sandpaper for 10 minutes, #1200 waterproof sandpaper for 10 minutes, #2000 waterproof sandpaper for 5 minutes, 9μm silicon carbide film for 10 minutes, 5μm aluminum oxide film for 10 minutes, 3μm aluminum oxide film for 5 minutes, 1μm aluminum oxide film for 5 minutes, and colloidal silica (Baikalox 0.1CR) with a particle size of 0.1μm using polishing paper foamed polyurethane for 5 minutes, and water is added at about 7mL / min during each grinding. After the ground sample is electronically stained with phosphotungstic acid, it is observed using a scanning electron microscope (SEM), and image analysis is performed using software such as ImageJ to obtain the distribution. Regarding the occupancy ratio of thermoplastic resin, any 10 points can be observed, and the occupancy ratio can be obtained from the average value.
[0115] Regarding the volume ratio of the continuous reinforcing fiber to the synthetic resin, for example, the thermoplastic resin, the higher the Vf, the higher the strength of the molded body. Therefore, in the continuous fiber reinforced resin molded body of the present embodiment, the volume content Vf of the continuous reinforcing fiber in the continuous fiber reinforced resin molded body is preferably 40% or more, more preferably 45% or more, further preferably 50% or more, further preferably 55% or more, and most preferably 65% or more. In the fiber reinforced resin molded body of the prior art, even if Vf is increased, the above-mentioned void ratio is still high, and the tensile stress (tensile strength) and flexural modulus (flexural rigidity) of the molded product cannot be increased. However, in the continuous fiber reinforced resin molded body of the present embodiment, by reducing the void ratio, the synthetic resin impregnation rate in the continuous fiber reinforced resin composite at Vf50% is 99% or more, the tensile stress is 525MPa or more, and the flexural modulus is 27GPa or more, and the synthetic resin impregnation rate is 99% or more, the tensile stress is 600MPa or more, and the flexural modulus is 35GPa or more at Vf65% can be achieved at the same time.
[0116] When the continuous reinforcing fiber is a glass fiber, the tensile stress of the continuous fiber reinforced resin molded body is preferably 480MPa or more, more preferably 525MPa or more, further preferably 600MPa or more, and most preferably 620MPa or more, based on the average value of the glass fiber when tested in each direction of the substantial orientation. In addition, the bending modulus of the continuous fiber reinforced resin molded body is preferably 22GPa or more, more preferably 27GPa or more, further preferably 30GPa or more, and most preferably 35GPa or more, based on the average value of the glass fiber when tested in each direction of the substantial orientation. At this time, the tensile stress and bending modulus are the values of the continuous reinforcing fibers contained in the continuous fiber reinforced resin molded body when they are substantially oriented in two directions, and are the average values of the values tested in two directions parallel to the continuous reinforcing fibers. In the case of a three-way material, it is preferably 2 / 3 times the stress or rigidity, and in the case of an n-way material, it is preferably 2 / n times the stress or rigidity.
[0117] When the continuous reinforcing fiber is a glass fiber, the value obtained by multiplying the average value of the tensile stress of the glass fiber of the continuous fiber reinforced resin molded body when tested in each direction of the substantial orientation by the number of directions in which the glass fiber is substantially oriented is preferably 960 MPa or more, more preferably 1050 MPa or more, further preferably 1200 MPa or more, and most preferably 1240 MPa or more. In addition, the value obtained by multiplying the average value of the bending stress of the glass fiber of the continuous fiber reinforced resin molded body when tested in each direction of the substantial orientation by the number of directions in which the glass fiber is substantially oriented is preferably 1260 MPa or more, more preferably 1400 MPa or more, further preferably 1600 MPa or more, and most preferably 1700 MPa or more. In addition, the value obtained by multiplying the bending modulus of the continuous fiber reinforced resin molded body by the number of directions in which the glass fiber is substantially oriented is preferably 44 GPa or more, more preferably 54 GPa or more, further preferably 60 GPa or more, and most preferably 70 GPa or more. The elasticity index of the continuous fiber-reinforced resin molded product defined by the following formula is preferably 1.2 or more, more preferably 1.3 or more, further preferably 1.4 or more, further preferably 1.5 or more, and most preferably 1.58 or more.
[0118] Elasticity index = (average value of elastic modulus of glass fiber in the direction parallel to the direction of substantial orientation × number of directions in which glass fiber is substantially oriented) / (Vf × elastic modulus of glass fiber)
[0119] [Acoustic Emission (AE) Method]
[0120] The continuous fiber-reinforced resin molded body of the present embodiment has a strength of fracture initiation due to interlaminar delamination measured by an acoustic emission method of preferably 40 MPa or more, more preferably 50 MPa or more.
[0121] The acoustic emission measurement can be performed by installing an AE sensor in the interlaminar shear test (JIS K7078).
[0122] [Morphology of continuous fiber reinforced resin molded body]
[0123] The form of the continuous fiber reinforced resin molded body is not particularly limited, and the following various forms can be cited. For example, the form can be cited: a form in which a woven or knitted fabric, a braid, or a tubular product of reinforcing fibers is compounded with a resin; a form in which reinforcing fibers pulled in one direction are compounded with a resin; a form in which yarns composed of reinforcing fibers and resin are pulled in one direction and molded; a form in which yarns composed of reinforcing fibers and resin are formed into a woven fabric, a knitted fabric, a braid, or a tubular product.
[0124] Examples of the intermediate material before molding of the continuous fiber reinforced resin molded body include: mixed yarns of continuous reinforcing fibers and resin fibers; coated yarns formed by covering the periphery of a bundle of continuous reinforcing fibers with resin; a form in which the continuous reinforcing fibers are pre-impregnated with resin to form a strip; a form in which the continuous reinforcing fibers are sandwiched between resin films; a form in which resin powder is attached to the continuous reinforcing fibers; a form in which a bundle of continuous reinforcing fibers is used as a core material and is braided with resin fibers around it; a form in which the spaces between the bundles of reinforcing fibers are pre-impregnated with resin; and the like.
[0125] [Method for producing continuous fiber reinforced resin molded body (composite material)]
[0126] The method for producing the continuous fiber reinforced resin composite material of the present embodiment preferably includes the following steps:
[0127] A step of heating and pressing a continuous reinforcing fiber to which a sizing agent including a coupling agent, a bundling agent and a lubricant is added and a thermoplastic resin having a terminal functional group reactive with the coupling agent so as to reach a temperature not lower than the melting point of the thermoplastic resin; and
[0128] This is cooled to a temperature below the melting point of the thermoplastic resin to obtain a continuous fiber reinforced resin composite material as a molded product.
[0129] From the perspective of adhesion between the thermoplastic resin and the continuous reinforcing fibers, the amount of terminal functional groups in the continuous fiber-reinforced resin composite material after heat pressing is preferably less than the amount of terminal functional groups contained in the thermoplastic resin before heat pressing, and the amount of terminal functional groups in the continuous fiber-reinforced resin composite material after heat pressing is more preferably 90% or less of the amount of terminal functional groups contained in the thermoplastic resin before heat pressing, and further preferably 85% or less.
[0130] From the viewpoint of reactivity between the coupling agent of the sizing agent and the terminal functional group of the thermoplastic resin, the flow rate of the thermoplastic resin during heat pressing is preferably 10% or less, more preferably 8% or less, further preferably 5% or less, and most preferably 3% or less.
[0131] Regarding the reactive terminal functional group, for example, when polypropylene is used as the thermoplastic resin, maleic acid or the like may be grafted onto the polypropylene resin as the main component.
[0132] The flow rate of the thermoplastic resin during heat pressing is calculated from (the weight of burrs of the thermoplastic resin generated during heat pressing) / (the weight of the thermoplastic resin before heat pressing).
[0133] The method of heating and pressing is not particularly limited. From the perspective of productivity, a heating and pressing method using a double belt press is preferred. With respect to the substrate, the reinforcing fibers and the thermoplastic resin may be fed from two or more rollers and fed into a double belt press device, or the reinforcing fibers cut into a desired size and the thermoplastic resin may be overlapped in the desired number of sheets and then fed. In this case, a guiding sheet (e.g., a Teflon (registered trademark) sheet) may also be fed in front of and behind the substrate.
[0134] As another heating pressing method, heating pressing using a mold can be preferably cited. The pressing method using a mold is not particularly limited, and the following various methods can be cited. For example, the substrate constituting the continuous fiber reinforced resin molded body is cut according to the desired molded body, and the required number of layers are stacked in consideration of the thickness of the target product, and the mold shape is set.
[0135] The cutting of the substrate can be performed piece by piece, or after the desired number of sheets are overlapped. From the aspect of productivity, it is preferred to cut in an overlapping state. The cutting method can be any method, for example, a water jet, a blade press, a hot blade press, a laser machine, a cutting plotter, etc. are cited. Preferably, a hot blade press with excellent cross-sectional shape and good handling properties by fusing the end faces when cutting multiple sheets overlapped is used. The appropriate cutting shape can also be adjusted by repeated trial and error, but is preferably set by simulation based on CAE (computer-aided engineering) according to the shape of the mold.
[0136] After placing the substrate in the mold, the mold is closed for pressing (compression). Afterwards, the mold temperature is adjusted to a temperature above the melting point of the thermoplastic resin constituting the continuous fiber reinforced resin molded body, so that the thermoplastic resin is melted for shaping. The mold clamping pressure is not particularly limited, and is preferably above 1 MPa, and more preferably above 3 MPa. In addition, the mold may be temporarily closed for venting, etc., and the mold clamping pressure may be temporarily released after compression molding. From the perspective of performance strength, the time for compression molding is preferably a longer time within the range where the thermoplastic resin used does not thermally deteriorate. From the perspective of productivity, the suitable time is preferably within 2 minutes, and more preferably within 1 minute.
[0137] In the manufacturing process of the continuous fiber reinforced resin molded body, a substrate is placed in a mold, the mold is closed and pressurized, and after a specified time, a specified thermoplastic resin composition is further injected and filled for molding, so that the thermoplastic resin and the specified thermoplastic resin composition are bonded, thereby manufacturing a hybrid molded body.
[0138] The timing of injection filling of the prescribed thermoplastic resin composition has a great influence on the interfacial strength between the two thermoplastic resins. The timing of injection filling of the prescribed thermoplastic resin composition is preferably within 30 seconds after the substrate is placed in the mold, the mold is closed, and the mold temperature is raised to a temperature above the melting point or glass transition temperature of the thermoplastic resin.
[0139] The mold temperature when injecting and filling the prescribed thermoplastic resin composition is preferably equal to or higher than the melting point or glass transition temperature of the thermoplastic resin constituting the continuous fiber reinforced resin molded body. More preferably, it is equal to or higher than the melting point of the thermoplastic resin constituting the continuous fiber reinforced resin molded body + 10°C or glass transition temperature + 10°C, further preferably, it is equal to or higher than the melting point + 20°C or glass transition temperature + 20°C, and even more preferably, it is equal to or higher than the melting point + 30°C or glass transition temperature + 30°C.
[0140] In the hybrid molded body, the bonded portion of the thermoplastic resin constituting the continuous fiber-reinforced resin molded body and the thermoplastic resin composition formed by injection molding preferably forms a concavo-convex structure in which they are mixed with each other.
[0141] In order to improve the interface strength, it is effective to set the mold temperature to the melting point of the injected thermoplastic resin composition or to increase the resin holding pressure during injection molding (for example, to 1 MPa or more). In order to improve the interface strength, it is preferred to set the holding pressure to 5 MPa or more, and more preferably to set the holding pressure to 10 MPa or more.
[0142] From the viewpoint of improving the interface strength, the pressure holding time is preferably extended, for example, to 5 seconds or more, preferably 10 seconds or more, and more preferably the holding time is until the mold temperature reaches or below the melting point of the thermoplastic resin composition.
[0143] [Resin for injection molding]
[0144] The thermoplastic resin composition for injection molding used for producing the hybrid molded body is not particularly limited as long as it is a thermoplastic resin composition commonly used in injection molding.
[0145] Examples of the thermoplastic resin composition include, but are not limited to, polyethylene, polypropylene, polyvinyl chloride, acrylic resins, styrene resins, polyethylene terephthalate, polybutylene terephthalate, polyarylate, polyphenylene ether, modified polyphenylene ether resin, wholly aromatic polyester, polyacetal, polycarbonate, polyetherimide, polyethersulfone, polyamide resin, polysulfone, polyetheretherketone, polyetherketone, etc., or a resin composition in which two or more kinds are mixed.
[0146] Furthermore, various fillers may be blended into these thermoplastic resin compositions.
[0147] Examples of various fillers include short fibers and long fiber materials which are discontinuous reinforcement materials of the same material as the reinforcement fibers.
[0148] When glass short fibers or long fibers are used as the discontinuous reinforcing material, the same sizing agent as that applied to the continuous reinforcing fibers constituting the continuous fiber-reinforced resin molded body of the present embodiment can be used.
[0149] The sizing agent (sizing agent) preferably contains a (silane) coupling agent, a lubricant, and a sizing agent. The types of the (silane) coupling agent, the lubricant, and the sizing agent may be the same as those of the above-mentioned sizing agent for the continuous reinforcing fibers.
[0150] From the perspective of the interfacial strength between the continuous fiber reinforced resin molded body and the injection molded thermoplastic resin composition portion, the thermoplastic resin composition used in injection molding is preferably similar to the thermoplastic resin constituting the continuous fiber reinforced resin molded body, and more preferably the same material. Specifically, when polyamide 66 is used in the thermoplastic resin constituting the continuous fiber reinforced resin molded body, the resin material of the thermoplastic resin composition for injection molding is preferably polyamide 66.
[0151] Other methods include: a molding method in which a substrate is placed in a mold and compressed using a double-belt press; a method in which a mold frame is placed so as to surround the substrate and pressurized using a double-belt press for molding; a molding method in which a heating compression molding machine set at one or more temperatures and a cooling compression molding machine set at one or more temperatures are prepared, and a mold provided with the substrate is sequentially placed into the compression molding machines for molding; and the like.
[0152] [Resin impregnation rate of continuous fiber reinforced resin molded body]
[0153] like Figure 2 As shown in FIG. 1 , the impregnation rate of the thermoplastic resin in the continuous fiber reinforced resin molded body can be obtained by the ratio of the voids in the cross section of the continuous fiber reinforced resin molded body. Specifically, the continuous fiber reinforced resin molded body is cut at an arbitrary position, embedded in an epoxy resin or the like, polished, and then observed under an optical microscope. The image obtained is analyzed using analysis software to calculate the impregnation rate of the thermoplastic resin in the continuous fiber reinforced resin molded body.
[0154] like Figure 6 As shown, the impregnation rate (%) is calculated by the following formula when the specified area is set to 100%:
[0155] Impregnation rate (%) = {1-(void area / continuous reinforcing fiber bundle area)} × 100
[0156] From the viewpoint of strength and appearance, the impregnation rate of the continuous fiber-reinforced resin molded body of the present embodiment is preferably 98% or more, more preferably 99% or more, further preferably 99.5% or more, and most preferably 99.9% or more.
[0157] [Continuous reinforcing fiber]
[0158] As the continuous reinforcing fibers, materials used in ordinary continuous fiber-reinforced resin molded products can be used.
[0159] Examples of the continuous reinforcing fibers include, but are not limited to, glass fibers, carbon fibers, plant fibers, aramid fibers, ultra-high-strength polyethylene fibers, polybenzopyrrole fibers, liquid crystal polyester fibers, polyketone fibers, metal fibers, and ceramic fibers.
[0160] From the viewpoints of mechanical properties, thermal properties, and versatility, glass fiber, carbon fiber, plant fiber, and aramid fiber are preferred, and from the viewpoint of productivity, glass fiber is preferred.
[0161] When glass fiber is selected as continuous reinforcing fiber, a sizing agent can be used. The sizing agent (sizing agent) preferably contains a silane coupling agent, a lubricant and a bundling agent. By forming a sizing agent that forms a strong bond with the resin around the continuous reinforcing fiber, a continuous fiber reinforced resin molded body with less void ratio can be obtained. When a thermoplastic resin is used as a synthetic resin, the sizing agent is preferably a sizing agent for a thermoplastic resin. The sizing agent for a thermoplastic resin refers to a material in which the continuous reinforcing fiber is heated to 300°C at 30°C / min using an electric furnace, and after returning to room temperature, the rigidity of the continuous reinforcing fiber is not greater than the rigidity of the continuous reinforcing fiber before heating. Regarding the sizing agent for a thermoplastic resin, for example, when a polyamide resin is selected as a synthetic resin, as a silane coupling agent, it is necessary to select a coupling agent that is easy to bond the carboxyl group as the terminal group of the polyamide resin to the amino group. Specifically, for example, γ-aminopropyltrimethoxysilane and epoxysilane can be cited.
[0162] As the bundling agent, it is necessary to use a resin that has good wettability with the polyamide resin or has a surface tension close to that of the polyamide resin. Specifically, for example, an emulsion of a polyurethane resin, an emulsion of a polyamide resin, or a modified product thereof can be selected. As the lubricant, it is necessary to use a substance that does not interfere with the silane coupling agent and the bundling agent, for example, carnauba wax can be cited.
[0163] From the perspective of the impregnation of the thermoplastic resin into the continuous reinforcing fibers, the sizing agent is preferably diffused into the thermoplastic resin by 50% or more during heating and pressing, and the ratio is more preferably 70% or more, further preferably 80% or more, and as long as it is 90% or more. The diffusion of the sizing agent can be determined by dissolving the matrix resin in the molded product using a good solvent and performing XPS measurement on the remaining reinforcing fibers; when the matrix resin is polyamide, HFIP and phenol are preferably used.
[0164] More than 90% of the sizing agent diffuses into the thermoplastic resin during heating and pressing, and when the terminal groups reactive with the coupling agent in the terminal functional groups of the thermoplastic resin decrease before and after heating and pressing, the coupling agent bonds with the terminal functional groups of the thermoplastic resin.
[0165] The continuous reinforcing fibers may be coated with a catalyst that promotes the reaction between the coupling agent and the terminal functional group of the thermoplastic resin. Examples of the catalyst include phosphoric acids such as sodium hypophosphite that promote the bonding reaction between the amino group of the silane coupling agent and the carboxyl group that is the terminal group of the polyamide resin when, for example, glass fibers are selected as the continuous reinforcing fibers and polyamide resins are selected as the thermoplastic resin.
[0166] [Silane coupling agent]
[0167] Silane coupling agents are usually used as surface treatment agents for glass fibers to help improve interfacial bonding strength.
[0168] As silane coupling agents, there can be mentioned, but not limited to, aminosilanes such as γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, etc.; mercaptosilanes such as γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane; epoxysilanes; vinylsilanes, maleic acids, etc. When polyamide is used as the synthetic resin, aminosilanes and maleic acids are preferred, and when epoxy resin is used as the synthetic resin, epoxysilanes are preferred.
[0169] [Lubricant]
[0170] Lubricants help improve the fiber opening properties of glass fibers.
[0171] As a lubricant, any conventional liquid or solid lubricating material corresponding to the purpose can be used, including but not limited to animal, plant or mineral waxes such as carnauba wax and lanolin wax; surfactants such as fatty amides, fatty acid esters, fatty acid ethers, aromatic esters, aromatic ethers, etc.
[0172] [Bundling agent]
[0173] Bunching agents help to improve the bundling of glass fibers and enhance interfacial bonding strength.
[0174] As the bundling agent, a polymer or thermoplastic resin can be used according to the purpose.
[0175] Examples of polymers used as the bundling agent include, but are not limited to, homopolymers of acrylic acid, copolymers of acrylic acid and other copolymerizable monomers, and salts of these with primary, secondary and tertiary amines, etc. In addition, polyurethane resins synthesized from isocyanates and polyester or polyether diols, such as m-xylene diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate) and isophorone diisocyanate, are also suitable.
[0176] As the homopolymer of acrylic acid, the weight average molecular weight is preferably 1,000 to 90,000, more preferably 1,000 to 25,000.
[0177] As copolymerizable monomers constituting the copolymer of acrylic acid and other copolymerizable monomers, for example, but not limited to, one or more monomers selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, vinylacetic acid, crotonic acid, methacrylic acid, fumaric acid, itaconic acid, citraconic acid and mesaconic acid among monomers having hydroxyl and / or carboxyl groups (excluding the case of only acrylic acid). As copolymerizable monomers, it is preferred to have one or more ester monomers.
[0178] Examples of salts of homopolymers and copolymers of acrylic acid with primary, secondary and tertiary amines include, but are not limited to, triethylamine salts, triethanolamine salts, glycine salts, etc. From the perspective of improving the stability of a mixed solution with other co-used chemical reagents (silane coupling agents, etc.) and reducing amine odor, the degree of neutralization is preferably 20 to 90%, more preferably 40 to 60%.
[0179] The weight average molecular weight of the acrylic acid polymer forming the salt is not particularly limited, but is preferably in the range of 3,000 to 50,000. It is preferably 3,000 or more to improve the bundling properties of the glass fibers, and is preferably 50,000 or less to improve the properties when formed into a composite molded body.
[0180] Thermoplastic resins used as bundling agents include, but are not limited to, polyolefin resins, polyamide resins, polyacetal resins, polycarbonate resins, polyester resins, polyetherketones, polyetheretherketones, polyethersulfones, polyphenylene sulfides, thermoplastic polyetherimides, thermoplastic fluorine resins, and modified thermoplastic resins obtained by modifying these resins. When the thermoplastic resin used as the bundling agent is the same thermoplastic resin and / or modified thermoplastic resin as the resin surrounding the continuous reinforcing fibers, the adhesion between the glass fibers and the thermoplastic resin is improved after the composite molded body is formed.
[0181] In addition, in order to further improve the adhesion between the continuous reinforcing fibers and the thermoplastic resin coating the continuous reinforcing fibers and to attach the sizing agent to the glass fibers in the form of an aqueous dispersion, the thermoplastic resin used as the sizing agent is preferably a modified thermoplastic resin from the perspective of reducing the proportion of the emulsifier component or eliminating the need for an emulsifier.
[0182] Here, the modified thermoplastic resin refers to a material in which the hydrophilicity, crystallinity, thermodynamic properties, etc. are modified by copolymerizing different monomer components in addition to the monomer components that can form the main chain of the thermoplastic resin for the purpose of changing the properties of the thermoplastic resin.
[0183] Examples of the modified thermoplastic resin used as the bundling agent include, but are not limited to, modified polyolefin resins, modified polyamide resins, and modified polyester resins.
[0184] The modified polyolefin resin used as the bundling agent is a copolymer of an olefin monomer such as ethylene or propylene and a monomer copolymerizable with the olefin monomer such as an unsaturated carboxylic acid, and can be produced by a known method. It can be a random copolymer formed by copolymerizing an olefin monomer with an unsaturated carboxylic acid, or a graft copolymer formed by grafting an unsaturated carboxylic acid onto an olefin.
[0185] As the olefin monomer, for example, ethylene, propylene, 1-butene, etc. can be cited, but not limited to. They can be used alone or in combination of two or more. As the monomer that can be copolymerized with the olefin monomer, for example, acrylic acid, maleic acid, maleic anhydride, methacrylic acid, vinyl acetic acid, butyric acid, isomethacrylic acid, fumaric acid, itaconic acid, citraconic acid, unsaturated carboxylic acids such as mesaconic acid, etc. can be cited, and they can be used alone or in combination of two or more.
[0186] As the copolymerization ratio of the olefin monomer and the monomer copolymerizable with the olefin monomer, assuming that the total mass of the copolymer is 100 mass%, preferably the olefin monomer is 60 to 95 mass%, the monomer copolymerizable with the olefin monomer is 5 to 40 mass%, and more preferably the olefin monomer is 70 to 85 mass%, the monomer copolymerizable with the olefin monomer is 15 to 30 mass%. When the olefin monomer is 60 mass% or more, the affinity with the matrix is good; in addition, when the mass% of the olefin monomer is 95 mass% or less, the water dispersibility of the modified polyolefin resin is good, and it is easy to uniformly impart to the continuous reinforcing fiber.
[0187] In the modified polyolefin resin used as a bundling agent, the modified groups such as carboxyl groups introduced by copolymerization can be neutralized by a basic compound. Examples of the basic compound include, but are not limited to, bases such as sodium hydroxide and potassium hydroxide; ammonia; and amines such as monoethanolamine and diethanolamine. The weight average molecular weight of the modified polyolefin resin used as a bundling agent is not particularly limited, but is preferably 5,000 to 200,000, and more preferably 50,000 to 150,000. From the perspective of improving the bundling properties of the glass fiber, it is preferably 5,000 or more, and from the perspective of emulsification stability when made into an aqueous dispersion, it is preferably 200,000 or less.
[0188] The modified polyamide resin used as the bundling agent is a modified polyamide compound having a hydrophilic group such as a polyalkylene oxide chain or a tertiary amine component introduced into the molecular chain, and can be produced by a known method.
[0189] When a polyalkylene oxide chain is introduced into the molecular chain, for example, a part or all of polyethylene glycol or polypropylene glycol is modified into diamine or dicarboxylic acid and the resulting modified product is copolymerized to produce the product. When a tertiary amine component is introduced, for example, aminoethylpiperazine, bisaminopropylpiperazine, α-dimethylaminoε-caprolactam, etc. are copolymerized to produce the product.
[0190] The modified polyester resin used as the bundling agent is a copolymer of a polycarboxylic acid or its anhydride and a polyol and has a hydrophilic group in its molecular skeleton including the terminal. The resin can be produced by a known method.
[0191] Examples of the hydrophilic group include polyalkylene oxide, sulfonate, carboxyl, neutralized salts thereof, etc. Examples of the polycarboxylic acid or its anhydride include aromatic dicarboxylic acids, aromatic dicarboxylic acids containing sulfonate, aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, trifunctional or higher polycarboxylic acids, etc.
[0192] Examples of the aromatic dicarboxylic acid include, but are not limited to, phthalic acid, terephthalic acid, isophthalic acid, phthalic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, and phthalic anhydride.
[0193] Examples of the sulfonate-containing aromatic dicarboxylic acid include, but are not limited to, sulfoterephthalate, 5-sulfoisophthalate, and 5-sulfophthalate.
[0194] Examples of the aliphatic dicarboxylic acid or alicyclic dicarboxylic acid include, but are not limited to, fumaric acid, maleic acid, itaconic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, dimer acid, 1,4-cyclohexanedicarboxylic acid, succinic anhydride, and maleic anhydride.
[0195] Examples of the trifunctional or higher polycarboxylic acid include, but are not limited to, trimellitic acid, pyromellitic acid, trimellitic anhydride, and pyromellitic dianhydride.
[0196] Among these, from the aspect of improving the heat resistance of the modified polyester resin, it is preferred that 40 to 99 mol% of the total polycarboxylic acid components are aromatic dicarboxylic acids. In addition, from the aspect of emulsification stability when the modified polyester resin is made into an aqueous dispersion, it is preferred that 1 to 10 mol% of the total polycarboxylic acid components are aromatic dicarboxylic acids containing sulfonates.
[0197] Examples of the polyol constituting the modified polyester-based resin include diols and trifunctional or higher-functional polyols.
[0198] Examples of the diol include, but are not limited to, ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, polybutylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, polytetramethylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, bisphenol A or its alkylene oxide adducts, etc. Examples of the trifunctional or higher polyol include trimethylolpropane, glycerol, pentaerythritol, etc.
[0199] As for the copolymerization ratio of the polycarboxylic acid or its anhydride and the polyol constituting the modified polyester resin, assuming that the total mass of the copolymer components is 100 mass%, preferably the polycarboxylic acid or its anhydride is 40 to 60 mass% and the polyol is 40 to 60 mass%, and more preferably the polycarboxylic acid or its anhydride is 45 to 55 mass% and the polyol is 45 to 55 mass%.
[0200] The weight average molecular weight of the modified polyester resin is preferably 3,000 to 100,000, more preferably 10,000 to 30,000. It is preferably 3,000 or more from the viewpoint of improving the bundling property of the glass fibers, and is preferably 100,000 or less from the viewpoint of emulsification stability when formed into an aqueous dispersion.
[0201] The polymer or thermoplastic resin used as the bundling agent may be used alone or in combination of two or more.
[0202] Assuming the total amount of the slinging agent is 100 mass %, at least 50 mass % and at least 60 mass % of one or more polymers selected from homopolymers of acrylic acid, copolymers of acrylic acid and other copolymerizable monomers, and salts of these with primary, secondary and tertiary amines are preferably used.
[0203] [Composition of sizing agent for glass fiber]
[0204] When glass fibers are used as continuous reinforcing fibers, the sizing agent of the glass fibers preferably contains 0.1 to 2 mass % of a silane coupling agent, 0.01 to 1 mass % of a lubricant, and 1 to 25 mass % of a sizing agent, and these components are preferably diluted with water to adjust the total mass to 100 mass %.
[0205] The amount of the silane coupling agent blended in the sizing agent for glass fibers is preferably 0.1 to 2% by mass, more preferably 0.1 to 1% by mass, and even more preferably 0.2 to 0.5% by mass, from the viewpoint of improving the bundling properties of the glass fibers and the interfacial bonding strength, and improving the mechanical strength of the composite molded product.
[0206] From the perspective of imparting sufficient lubricity, the amount of lubricant blended into the sizing agent for glass fibers is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and from the perspective of increasing interfacial bonding strength and increasing the mechanical strength of the composite molded body, the amount is preferably 1% by mass or less, more preferably 0.5% by mass or less.
[0207] From the viewpoint of controlling the bundling property of the glass fibers and improving the interfacial bonding strength and improving the mechanical strength of the composite molded body, the amount of the sizing agent blended in the sizing agent for the glass fibers is preferably 1 to 25% by mass, more preferably 3 to 15% by mass, and even more preferably 3 to 10% by mass.
[0208] [How to use sizing agents for glass fibers]
[0209] The sizing agent for glass fiber can be prepared in any form such as an aqueous solution, a colloidal dispersion, or an emulsion using an emulsifier depending on the usage mode. From the perspective of improving the dispersion stability and heat resistance of the sizing agent, it is preferably prepared in the form of an aqueous solution.
[0210] The glass fibers constituting the continuous reinforcing fiber resin molded body of the present embodiment are continuously obtained by applying the above-mentioned sizing agent to the glass fibers using a known method such as a roll coater in a known glass fiber production process and drying the produced glass fibers.
[0211] The sizing agent is preferably added in an amount of 0.1 to 3 mass %, more preferably 0.2 to 2 mass %, and further preferably 0.2 to 1 mass % based on the total mass of the silane coupling agent, lubricant, and sizing agent relative to 100 mass % of the glass fiber.
[0212] From the perspective of controlling the bundling properties of the glass fibers and improving the interfacial bonding strength, the amount of the sizing agent added is preferably 0.1% by mass or more based on the total mass of the silane coupling agent, lubricant and bundling agent relative to 100% by mass of the glass fibers, and is preferably 3% by mass or less from the perspective of yarn handling properties.
[0213] It should be noted that, when carbon fibers are selected as continuous reinforcing fibers, the sizing agent preferably contains a coupling agent, a lubricant, and a bundling agent. There are no particular restrictions on the types of sizing agents, lubricants, and bundling agents, and known substances can be used. As specific materials, materials described in Japanese Patent Gazette No. 2015-101794 can be used. As a coupling agent, a substance with good compatibility with the hydroxyl groups present on the surface of the carbon fibers can be selected, as a bundling agent, a substance with good wettability or close surface tension to the selected synthetic resin can be selected, and as a lubricant, a substance that does not hinder the coupling agent and the bundling agent can be selected.
[0214] When other continuous reinforcing fibers are used, the type and amount of sizing agents used in glass fibers and carbon fibers can be appropriately selected according to the properties of the continuous reinforcing fibers, and it is preferred to use the type and amount of sizing agents based on the sizing agents used in carbon fibers.
[0215] [Shape of continuous reinforcing fibers]
[0216] The continuous reinforcing fiber is a multifilament formed of a plurality of reinforcing fibers, and the number of single fibers is preferably 30 to 15,000 from the perspective of handling. From the perspective of strength and handling, the single fiber diameter of the continuous reinforcing fiber is preferably 2 to 30 μm, more preferably 4 to 25 μm, further preferably 6 to 20 μm, and most preferably 8 to 18 μm.
[0217] From the perspective of the handling properties of the composite yarn and the strength of the molded product, the single yarn diameter R (μm) and density D (g / cm 3 ) is preferably 5 to 100 μm·g / cm 3 , more preferably 10 to 50 μm·g / cm 3 , more preferably 15 to 45 μm·g / cm 3 , and more preferably 20 to 45 μm·g / cm 3 .
[0218] The density D can be measured using a densimeter. On the other hand, the single fiber diameter (μm) can be measured based on the density (g / cm 3 ) and fineness (dtex) and number of single yarns (roots) are calculated by the following formula.
[0219] [Number 1]
[0220]
[0221] In order to make the product RD of the continuous reinforcing fiber within a predetermined range, the fineness (dtex) and the number of filaments (roots) of the commercially available continuous reinforcing fiber can be appropriately selected according to the density of the continuous reinforcing fiber. For example, when glass fiber is used as the continuous reinforcing fiber, since the density is about 2.5 g / cm 3 , so a fiber with a single fiber diameter of 2 to 40 μm can be selected. Specifically, when the single fiber diameter of the glass fiber is 9 μm, by selecting a glass fiber with a fineness of 660 dtex and a single fiber number of 400, the product RD is 23. In addition, when the single fiber diameter of the glass fiber is 17 μm, by selecting a glass fiber with a fineness of 11,500 dtex and a single fiber number of 2,000, the product RD is 43. When carbon fiber is used as a continuous reinforcing fiber, since the density is about 1.8 g / cm 3 , so the fiber with a single fiber diameter of 2.8 to 55 μm can be selected. Specifically, when the single fiber diameter of the carbon fiber is 7 μm, by selecting a carbon fiber with a fineness of 2,000 dtex and a single fiber number of 3,000, the product RD is 13. When aramid fiber is used as the continuous reinforcing fiber, the density is about 1.45 g / cm 3 , so a fiber with a single-filament diameter of 3.4 to 68 μm can be selected. Specifically, when the single-filament diameter of the aramid fiber is 12 μm, the product RD is 17 by selecting an aramid fiber with a fineness of 1,670 dtex and a single-filament number of 1,000.
[0222] Continuous reinforcing fibers (e.g., glass fibers) are manufactured by measuring and mixing raw glass materials, making molten glass using a melting furnace, spinning the molten glass into glass fibers, applying a sizing agent, and passing through a spinning machine to produce the fibers in the form of direct untwisted roving (DWR), yarn cakes, twisted yarns, etc. The continuous reinforcing fibers may be in any form, but if they are curled into yarns, yarn cakes, or DWRs, the productivity and production stability in the process of coating with resins are improved, and therefore, they are preferred. From the perspective of productivity, DWRs are most preferred.
[0223] [Synthetic resin]
[0224] The synthetic resin constituting the matrix resin of the continuous fiber-reinforced resin molded body of the present embodiment may be a thermoplastic resin or a thermosetting resin, but is preferably a thermoplastic resin from the viewpoint of molding cycle and recyclability.
[0225] [Thermoplastic resin]
[0226] The thermoplastic resin constituting the continuous fiber reinforced resin molded body of the present embodiment may be used only one kind, or two or more kinds may be used in combination. From the aspect of adhesion to the continuous fiber reinforced resin, it is preferred to include more than two kinds of thermoplastic resins. In the case of including more than two kinds of thermoplastic resins, at the extreme interface between one continuous reinforcing fiber and the synthetic resin in the cross section orthogonal to the length direction of the continuous reinforcing fiber, in the peripheral outer region of one tenth of the radius of one continuous reinforcing fiber from the peripheral portion of the continuous reinforcing fiber, among the two or more thermoplastic resins, from the aspect of productivity and the interface strength between the reinforcing fiber and the resin, it is preferred that the proportion of the resin other than the resin with the highest proportion in the overall calculation of the resin area is higher than the proportion of the resin with the highest proportion in the overall calculation of the resin area.
[0227] From the aspect of the reactivity between the coupling agent and the terminal functional group of the thermoplastic resin, the water absorption of the thermoplastic resin is preferably 0.1 wt % or more, more preferably 0.3 wt % or more, further preferably 0.5 wt % or more, further preferably 0.8 wt % or more, further preferably 1.0 wt % or more, and most preferably 1.5 wt % or more. The water absorption of the thermoplastic resin can be measured using a Karl Fischer titrator or the like.
[0228] It is preferred to add a catalyst that promotes the reaction between the coupling agent and the terminal functional group of the thermoplastic resin to the thermoplastic resin. Examples of the catalyst include phosphoric acids such as sodium hypophosphite that promote the bonding reaction between the amino group of the silane coupling agent and the carboxyl group that is the terminal group of the polyamide resin, for example, when glass fibers are selected as the continuous reinforcing fibers and polyamide resins are selected as the thermoplastic resin.
[0229] From the perspective of mechanical strength of the continuous fiber reinforced resin composite material, the content of the particulate additive contained in the thermoplastic resin is preferably 30 ppm or less, more preferably 20 ppm or less, more preferably 10 ppm or less, and most preferably 5 ppm or less.
[0230] Examples of the particulate additive contained in the thermoplastic resin include carbon black and the like.
[0231] [Droplet generation coefficient]
[0232] The droplet generation coefficient is an index representing the compatibility of the resin and the reinforcing fiber. The droplet generation coefficient not only affects the main component of the resin, but also affects the trace components contained in the resin. The droplet generation coefficient of the thermoplastic resin and the reinforcing fiber is preferably more than 10 (when the number of contacts is 4). Regarding the droplet generation coefficient, for example, a composite material interface characteristic evaluation device (HM410, Toei Industry Co., Ltd.) can be used. When a monofilament of a reinforcing fiber is coated with resin, the resin is contacted with the reinforcing fiber for a plurality of times, and the number of droplets generated is counted and calculated by the following formula.
[0233] (Droplet generation coefficient) = {(Number of droplets generated) / (Number of times the resin comes into contact with the reinforcing fibers)}×10
[0234] [Two or more thermoplastic resins]
[0235] The thermoplastic resin constituting the matrix resin of the continuous fiber reinforced resin molded body of the present embodiment may be two or more kinds of thermoplastic resins. Among the two or more kinds of thermoplastic resins, the resin (main resin) having the highest proportion in the entire resin region is preferably 85% to 99% of the total area occupied by the two or more kinds of thermoplastic resins. From the perspective of heat resistance, among the two or more kinds of thermoplastic resins, the resin (main resin) having the highest proportion in the entire resin region is preferably the resin with the highest melting point.
[0236] Among the two or more thermoplastic resins, the difference between the melting point of the resin with the highest melting point and the melting point of the resin with the lowest melting point is preferably 35°C or more, more preferably 100°C or more. The type of thermoplastic resin contained in the continuous fiber reinforced resin molded body can be determined by analyzing the cross section of the continuous fiber reinforced resin molded body using a laser Raman microscope, and the melting point and glass transition temperature of each thermoplastic resin can be calculated using a differential scanning calorimeter (DSC) based on the composition of the resin. In addition, from the perspective of heat resistance, it is preferred that the melting point of the mixture of thermoplastic resins is the same as the melting point of the resin (main resin) that occupies the highest proportion of the entire resin region among the thermoplastic resins.
[0237] If the difference between the heating melting peak temperature and the cooling crystallization peak temperature of the mixture of two or more thermoplastic resins constituting the continuous fiber reinforced resin molded body of the present embodiment is smaller than the difference between the heating melting peak temperature and the cooling crystallization peak temperature of the resin (main resin) that occupies the highest proportion of the entire resin region among the resins constituting the two or more thermoplastic resins, the balance between moldability and impregnation rate is excellent, which is preferred. The heating melting peak temperature and the cooling crystallization peak temperature can be calculated by DSC.
[0238] Among the two or more thermoplastic resins constituting the continuous fiber reinforced resin molded body of the present embodiment, it is preferred that the bonding force between at least one resin (secondary resin) other than the resin (main resin) having the highest proportion in the entire resin region and the continuous reinforcing fibers is greater than the bonding force between the resin (main resin) having the highest proportion in the entire resin region and the continuous reinforcing fibers from the perspective of impregnation and strength. The bonding force between each thermoplastic resin and the continuous reinforcing fibers can be obtained by an ejection test using a nanoindenter.
[0239] Among the two or more thermoplastic resins constituting the continuous fiber reinforced resin molded body of the present embodiment, from the perspective of impregnation and strength, it is preferred that the difference in surface tension between at least one resin (secondary resin) other than the resin (main resin) with the highest proportion in the entire resin region and the above-mentioned continuous reinforcing fibers is smaller than the difference in surface tension between the resin (main resin) with the highest proportion in the entire resin region and the continuous reinforcing fibers. In addition, among the two or more thermoplastic resins constituting the continuous fiber reinforced resin molded body of the present embodiment, from the perspective of impregnation and strength, it is preferred that the wettability of at least one resin (secondary resin) other than the resin (main resin) with the highest proportion in the entire resin region to the continuous reinforcing fibers is greater than the wettability of the resin (main resin) with the highest proportion in the entire resin region to the continuous reinforcing fibers. The difference in surface tension and wettability between each thermoplastic resin and the continuous reinforcing fibers can be evaluated by burying one continuous reinforcing fiber in a thermoplastic resin melted on a hot plate and by the length of the thermoplastic resin stretched by the continuous fiber when the continuous reinforcing fiber is extracted.
[0240] For the reason of excellent balance between strength and impregnation, the melt viscosity of the mixture of two or more thermoplastic resins constituting the continuous fiber reinforced resin molded body of the present embodiment is preferably the same as the melt viscosity of the resin (main resin) that occupies the highest proportion in the entire resin region among the two or more thermoplastic resins. The melt viscosity of the resin can be measured using a double capillary rheometer or the like.
[0241] The two or more thermoplastic resins constituting the continuous fiber-reinforced resin molded article of the present embodiment may be pre-mixed and used according to the form of an intermediate material, or may be dry-blended to form the resin form of the intermediate material.
[0242] [Form of thermoplastic resin]
[0243] The form of the thermoplastic resin is not particularly limited, and examples thereof include a film, a pellet, a fiber, a plate, a powder, and a form coated with reinforcing fibers.
[0244] [One or more types of thermoplastic resins]
[0245] Thermoplastic resins include, but are not limited to, polyolefin resins such as polyethylene and polypropylene; polyamide resins such as polyamide 6, polyamide 66, and polyamide 46; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polypropylene terephthalate; polyacetal resins such as polyoxymethylene; polycarbonate resins; polyether resins such as polyether ketone, polyether ether ketone, polyether glycol, polypropylene glycol, and polytetramethylene ether glycol; polyether sulfone; polyphenylene sulfide; thermoplastic polyetherimide; thermoplastic fluorine resins such as tetrafluoroethylene-ethylene copolymer; polyurethane resins; acrylic resins; and modified thermoplastic resins obtained by modifying them.
[0246] Among these thermoplastic resins, polyolefin resins, polyamide resins, polyester resins, polyether resins, polyether sulfones, polyphenylene sulfide, thermoplastic polyether imide, and thermoplastic fluorine resins are preferred. From the perspective of mechanical properties and versatility, polyolefin resins, modified polyolefin resins, polyamide resins, polyester resins, polyurethane resins, and acrylic resins are more preferred. If the thermal properties are taken into account, polyamide resins and polyester resins are further preferred. In addition, from the perspective of durability against repeated loads, polyamide resins are further preferred.
[0247] [Polyester resin]
[0248] The polyester resin refers to a polymer compound having a -CO-O- (ester) bond in the main chain.
[0249] Examples of the polyester resin include, but are not limited to, polyethylene terephthalate, polybutylene terephthalate, polybutylene terephthalate, poly-1,4-cyclohexyl dimethylene terephthalate, and polyethylene 2,6-naphthalene dicarboxylate.
[0250] The polyester-based resin may be a homopolyester or a copolyester.
[0251] In the case of copolymerized polyester, it is preferred to appropriately copolymerize the third component with the homopolyester. Examples of the third component include, but are not limited to, diol components such as diethylene glycol, neopentyl glycol, and polyalkylene glycol, and dicarboxylic acid components such as adipic acid, sebacic acid, phthalic acid, isophthalic acid, and 5-(sodiosulfo)isophthalic acid.
[0252] In addition, polyester resins using raw materials derived from biomass can also be used, including but not limited to aliphatic polyester resins such as polylactic acid, polybutylene succinate, and polybutylene succinate adipate, and aromatic polyester resins such as polybutylene adipate.
[0253] [Polyamide resin]
[0254] Polyamide resin refers to a polymer compound having a -CO-NH- (amide) bond in the main chain. Examples thereof include aliphatic polyamides, aromatic polyamides, and fully aromatic polyamides. From the perspective of affinity with reinforcing fibers and the ease of obtaining a high reinforcing effect based on reinforcing fibers, aliphatic polyamides are preferred.
[0255] From the viewpoint of adhesion between the resin and the reinforcing fibers, the amount of carboxyl terminal groups contained in the polyamide resin is preferably 65 μmol / g or more, more preferably 70 μmol / g or more, further preferably 75 μmol / g or more, and still more preferably 80 μmol / g or more.
[0256] From the viewpoint of adhesion between the resin and the reinforcing fibers, the amount of amino terminal groups contained in the polyamide resin is preferably 40 μmol / g or less, more preferably 35 μmol / g or less, further preferably 30 μmol / g or less, and still more preferably 25 μmol / g or less.
[0257] Examples of the polyamide resin include, but are not limited to, polyamides obtained by ring-opening polymerization of lactams, polyamides obtained by self-condensation of ω-aminocarboxylic acids, polyamides obtained by condensation of diamines and dicarboxylic acids, and copolymers thereof.
[0258] The polyamide-based resin may be used alone or as a mixture of two or more.
[0259] Examples of lactams include, but are not limited to, pyrrolidone, caprolactam, undecanolactam, and laurolactam. Examples of ω-aminocarboxylic acids include, but are not limited to, ω-amino fatty acids, which are ring-opening compounds of lactams based on water. Lactams or ω-aminocarboxylic acids may be prepared by combining two or more monomers to form condensed monomers.
[0260] Examples of the diamine (monomer) include, but are not limited to, linear aliphatic diamines such as 1,6-hexanediamine and 1,5-pentanediamine; branched aliphatic diamines such as 2-methyl-1,5-pentanediamine and 2-ethyl-1,6-hexanediamine; aromatic diamines such as p-phenylenediamine and m-phenylenediamine; and alicyclic diamines such as cyclohexanediamine, cyclopentanediamine and cyclooctanediamine.
[0261] Examples of dicarboxylic acids (monomers) include, but are not limited to, aliphatic dicarboxylic acids such as adipic acid, pimelic acid, and sebacic acid; aromatic dicarboxylic acids such as phthalic acid and isophthalic acid; and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid. The diamine and dicarboxylic acid as monomers may be used alone or in combination of two or more to be condensed.
[0262] Examples of polyamide resins include, but are not limited to, polyamide 4 (poly-α-pyrrolidone), polyamide 6 (polycaprolactam), polyamide 11 (polyundecanamide), polyamide 12 (polydodecaneamide), polyamide 46 (polybutylene adipamide), polyamide 66 (polyhexamethylene adipamide), polyamide 610, polyamide 612, polyamide 6T (polyhexamethylene terephthalamide), polyamide 9T (polynonane terephthalamide) and polyamide 6I (polyhexamethylene isophthalamide), and copolymer polyamides containing these as constituent components.
[0263] Examples of the copolymer polyamide include, but are not limited to, copolymers of hexamethylene adipamide and hexamethylene terephthalamide, copolymers of hexamethylene adipamide and hexamethylene isophthalamide, and copolymers of hexamethylene terephthalamide and 2-methylpentanediamine terephthalamide.
[0264] [Method for producing a continuous fiber reinforced composite material formed body]
[0265] A shaped body of a continuous fiber reinforced composite material can be manufactured by a method comprising the following steps, in which the continuous fiber reinforced resin composite material manufactured by the above method is heated to a temperature above the melting point of the above thermoplastic resin using an IR heater or the like, pressed using a mold or the like, and then cooled to a temperature below the melting point of the thermoplastic resin for shaping.
[0266] [Thermosetting resin]
[0267] Examples of the thermosetting resin include, but are not limited to, epoxy resins, phenol resins, melamine resins, urea resins, unsaturated polyester resins, etc. These thermosetting resins may be used alone or in combination of two or more.
[0268] [Application of the continuous fiber reinforced resin molded product (composite material) according to the present embodiment]
[0269] The continuous fiber-reinforced resin molded article of the present embodiment can be suitably used as a structural material for aircraft, vehicles, construction materials, robots, communication equipment casings, and the like.
[0270] In vehicle applications, it can be used for, but not limited to, chassis / frame, undercarriage, drive system components, interior components, exterior components, functional components, and other components.
[0271] Specifically, the present invention can be suitably used as the following parts: steering shaft, bracket, sunroof, pedal, roof trim, door trim, trunk, trunk lid, hood, seat frame, seat back, seat belt retractor, seat belt retractor support frame, clutch, gear, pulley, cam, AG shaft, elastic beam, buffer, lamp, reflector, glass window, front module, rear door inner panel, brake pedal, steering wheel, electrical equipment material, sound absorbing material, door exterior, interior panel, instrument panel, tailgate, top beam, seat, seat frame, wiper link, EPS (Electric Power Steering), small motor, radiator, ECU (Engine Control Unit) box, ECU cover, steering gear box cover, plastic cover, EV (Electric Vehicle, Electric Vehicle) motor frame, wiring group, on-board instrument, combination switch, small motor, spring, shock absorber, wheel, rim cover, frame, subframe, side frame, two-wheeled vehicle frame, fuel tank, oil pan, intake manifold, drive shaft, drive motor, single cabin, hydrogen tank, fuel cell electrode, panel, floor panel, outer panel, door, cabin, roof, hood, steam valve, EGR (exhaust gas recirculation,Exhaust Gas Recirculation) valve, variable valve timing unit, connecting rod, cylinder bore, beams (engine foot, front floor crossbeam, footrest crossbeam, seat crossbeam, inner side beam, rear crossbeam, suspension beam, pillar reinforcement beam, front side beam, front plate beam, upper plate beam, front panel crossbeam, steering column), tunnel, locking insert, gearbox, gearshift rail, bridge housing, roof rail, upper body, side rail, trim, door surround assembly, airbag parts, pillar, front panel to pillar support, suspension tower, bumper, body lower pillar, front pillar, reinforcement (instrument panel, rail, roof, front pillar, roof rail, roof side rail, storage box, door waistline, front floor lower layer, front body upper pillar, front body lower pillar, center pillar, center pillar hinge, door outer panel), side outer panel, front door window frame, MICS (Minimum Intrusion Cabin System components, torque box, radiator support, radiator fan, water pump, fuel pump, electronic control throttle body, engine control ECU, starter, alternator, manifold, gearbox, clutch, dash panel, dash panel insulation pad, door side impact beam, bumper beam, door beam, partition, outer pad, inner pad, rear seat bar, door panel, door trim subassembly, energy absorber (bumper, shock absorber), shock absorber, shock absorber trim, pillar trim, roof inner trim, resin rib, side rail front spacer , side rail rear spacer, seat belt pretensioner, airbag sensor, arm (suspension, lower arm, hood hinge), suspension link, shock absorber bracket, fender bracket, inverter bracket, inverter module, hood inner panel, hood panel, cowl vent, cowl top outer front panel, cowl top outer panel, floor muffler, shock absorber seat, hood insulation layer, fender side panel protector, cowl insulation layer, cowl top vent, cylinder head cover, tire deflector, fender support frame, engine room tie rod (strut tower bar), center channel (mission center tunnel), floor channel, radiator center support frame (Radiator core supports), trunk trim, trunk floor, accelerator pedal, accelerator pedal base and other parts. ,
[0272] The continuous fiber-reinforced resin molded article (composite material) of the present embodiment may be in the shape of, for example, a rectangular parallelepiped when used for a communication device housing.
[0273] As a characteristic of the shell, the shell is a component requiring radio wave transmittance, and the electric field shielding property measured by the KEC method is preferably less than 10 dB, more preferably less than 5 dB, and further preferably less than 0.1 dB at a frequency of 1 GHz. As the continuous reinforcing fiber having this characteristic, continuous reinforcing glass fiber can be used.
[0274] The average thickness of the shell is preferably 1 mm or less, more preferably 0.5 mm or less, and most preferably 0.4 mm or less. For example, by manufacturing through preforming, a shell of a desired thickness with little disorder of continuous fibers and no voids can be manufactured.
[0275] Example
[0276] The present invention will be specifically described below by way of examples and comparative examples, but the present invention is not limited to these examples and can of course be implemented with various modifications within the scope of the gist of the present invention.
[0277] First, practical measurement methods and the like used in Examples and Comparative Examples will be described.
[0278] [Average porosity in a region that is one-tenth the radius of one continuous reinforcing fiber from the end of one continuous reinforcing fiber]
[0279] The continuous fiber reinforced resin molded body was cut with a band saw, and the cut test piece was grinded with a grinder (Small Precision Sample Making System IS-POLISHER ISPP-1000 (Ikegami Seiki Co., Ltd.)) at a pressure of 400 g / cm 2 The grinding was performed in the manner of applying a force of 100°. During the grinding, the samples were sequentially ground with #220 water-resistant sandpaper for 10 minutes, #400 water-resistant sandpaper for 2 minutes, #800 water-resistant sandpaper for 5 minutes, #1200 water-resistant sandpaper for 10 minutes, #2000 water-resistant sandpaper for 15 minutes, 9 μm silicon carbide film for 15 minutes, 5 μm aluminum oxide film for 15 minutes, 3 μm aluminum oxide film for 15 minutes, 1 μm aluminum oxide film for 15 minutes, and 0.1 μm colloidal silica (Baikalox 0.1CR) using foamed polyurethane with polishing paper for 10 minutes, and the grinding was performed while adding water at about 7 mL / min during each grinding. The polished sample was observed using SEM (S-4700, Hitachi High-Technologies Co., Ltd.), and the porosity of the region of one tenth of the radius of one continuous reinforcing fiber was calculated from the obtained image. 100 randomly selected continuous reinforcing fibers were observed, and the average porosity of the region of one tenth of the radius of one continuous reinforcing fiber and the proportion of the porosity of 10% or less were determined.
[0280] [Impermeation rate]
[0281] The cross section of the molded body was cut out, embedded in epoxy resin, and carefully ground so that the continuous reinforcing fibers would not be damaged. The continuous reinforcing fiber bundle, synthetic resin, and void area were obtained from the obtained image, and the ratio of the void area to the continuous reinforcing fiber bundle (whole) area was calculated by the following formula.
[0282] Impregnation rate (%)={1-(void area / continuous reinforcing fiber bundle area)}×100.
[0283] [Tensile stress]
[0284] A strip-shaped test piece with a length of 70 mm, a width of 10 mm and a thickness of 2 mm was cut out from the molded body and clamped at intervals of 30 mm along the length direction using an INSTRON universal testing machine. The tensile stress (MPa) was measured at a speed of 5 mm / min, 23°C, and 50% RH and in a constant temperature bath at 150°C and 50%.
[0285] [Bending stress, bending modulus]
[0286] A strip-shaped test piece with a length of 100 mm, a width of 10 mm, and a thickness of 2 mm was cut out from the molded body. The bending stress (MPa) and the bending modulus (GPa) were measured using an INSTRON universal testing machine with a three-point bending fixture set to 32 mm at a speed of 1 mm / min, 23°C, and 50% RH.
[0287] [Measurement of the volume ratio (Vf) of reinforcing fibers in continuous fiber-reinforced resin and the ratio of the amount of resin leaking out during molding]
[0288] Cut out 2g of the continuous fiber reinforced resin molded body, put it into an electric furnace, and heat it at a temperature of 650°C for 3 hours to burn the resin. Then cool it naturally to room temperature, measure the mass of the remaining glass fiber, and thus find the ratio of glass fiber to resin contained in the continuous fiber reinforced resin molded body. In addition, divide the obtained ratio by the density to find the volume ratio (Vf) of the reinforcing fiber relative to the continuous fiber reinforced resin molded body. In addition, the amount of resin leaked during molding is calculated from the amount of resin put in and the amount of resin contained in the continuous fiber reinforced resin molded body after molding, and the amount of resin leaked is divided by the amount of resin put in to find the ratio of the amount of resin leaked.
[0289] [Type and proportion of each thermoplastic resin in two or more fiber-reinforced resins]
[0290] A cross section in the thickness direction (a cross section perpendicular to the length direction of the continuous reinforcing fibers) of the continuous fiber-reinforced resin molded body was cut out at any five locations, embedded in epoxy resin, and carefully ground so as not to damage the continuous reinforcing fibers.
[0291] The image of the cross section was taken using a laser Raman microscope (inViaQontor confocal Raman microscope; Renishaw Co., Ltd.), and the type of resin contained in the fiber-reinforced resin was determined from the obtained image and spectrum. In addition, the respective areas were calculated by image processing based on imageJ, and the occupancy ratio (area ratio) of the resin occupying the area of one tenth of the radius of one continuous reinforcing fiber from the end of one continuous reinforcing fiber was calculated. In addition, for any 10 continuous reinforcing fibers in the cross section, the area ratio of each resin occupying the area of one tenth of the radius of one continuous reinforcing fiber was calculated, and the average value was calculated.
[0292] [Distribution of Thermoplastic Resin in Resin Regions Other Than Polar Interface Regions in Fiber-Reinforced Resin Molded Article]
[0293] The continuous fiber reinforced resin molded body was subjected to a grinding process (Small Precision Sample Making System IS-POLISHERISPP-1000 (Ikegami Seiki Co., Ltd.)) at a grinding speed of 125 g / cm 2 The grinding was carried out in a manner of force. During the grinding, the samples were ground with #220 water-resistant sandpaper for 10 minutes, #1200 water-resistant sandpaper for 10 minutes, #2000 water-resistant sandpaper for 5 minutes, 9μm silicon carbide film for 10 minutes, 5μm aluminum oxide film for 10 minutes, 3μm aluminum oxide film for 5 minutes, 1μm aluminum oxide film for 5 minutes, and 0.1μm colloidal silica (Baikalox 0.1CR) using foamed polyurethane with polishing paper for 5 minutes, and water was added at about 7mL / min during each grinding. The sample obtained by grinding was carefully immersed in a 5wt% aqueous solution of 12tungsten (VI) phosphoric acid n-hydrate for 18 hours for electronic staining in a manner that the grinding surface would not collapse. After drying, the distribution of the thermoplastic resin in 5 random 50 μm×50 μm sections was observed using SEM (S-4700, Hitachi High-Technologies Co., Ltd.), and the area of each was calculated using image processing based on image J. Based on the obtained distribution, it was determined whether the specific resin was uniformly dispersed or mixed in the resin region other than the polar interface region.
[0294] [Measurement method of loss tangent of continuous fiber reinforced resin molded body]
[0295] The continuous fiber reinforced resin molded body with a thickness of 2 mm was cut into 5 mm wide and 60 mm long in the direction of 0° and 90° relative to the fiber direction using a band saw, and the deformation mode was measured in a torsion mode using a dynamic viscoelasticity measuring device (AresG2, TA Instruments Co., Ltd.) under a nitrogen atmosphere at a measuring temperature range of 30°C to 250°C, a heating rate of 5.0°C / min, and an angular frequency of 10 rad / s. The loss tangent at each temperature was plotted, and the value of the loss tangent and the temperature at this time were obtained from the peak value of the obtained curve and the temperature at this time. The value of the loss tangent is the value of the peak on the low temperature side.
[0296] [Surface impact test]
[0297] A test piece of 60 mm in length, 60 mm in width and 2 mm in thickness was cut out from the molded body and tested using a high-speed impact tester (Shimadzu HYDROSHOT HITS-P10, Shimadzu Corporation) in accordance with JIS K7211-2; 2006 under the conditions of a striker diameter of 20 mm Ф, a placement diameter of 40 mm Ф, a test speed of 4.4 m / sec, a test temperature of 23°C, and a test number of n = 5. A graph of the test force versus displacement was drawn, and the integral value until the maximum impact force was reached was calculated, and the average value of the five samples was taken as the impact absorption energy.
[0298] [Method for measuring storage modulus of torsional mode of continuous fiber reinforced resin molded body]
[0299] The continuous fiber reinforced resin molded body with a thickness of 2 mm was cut into a width of 5 mm and a length of 60 mm using a band saw along the direction of 0°, 90° or 45° (inclined direction) relative to the fiber direction, and the deformation mode was measured in a torsion mode using a dynamic viscoelasticity measuring device (AresG2, TAInstruments Co., Ltd.) in a nitrogen atmosphere at a measuring temperature range of 30°C to 250°C, a heating rate of 5.0°C / min, and an angular frequency of 10 rad / s. The storage modulus at each temperature was plotted, and the storage modulus value and the temperature at this time were obtained from the peak value of the obtained curve and the temperature at this time.
[0300] [Surface impact test]
[0301] A test piece of 60 mm in length, 60 mm in width and 2 mm in thickness was cut from the molded body and tested using a high-speed impact tester (SHIMADZU HYDROSHOT HITS-P10, SHIMADZU Corporation) in accordance with JIS K7211-2; 2006 under the conditions of a striker diameter of 20 mm Ф, a placement diameter of 40 mm Ф, a test speed of 4.4 m / sec, a test temperature of 23°C, and a test number n = 5. A graph of the test force versus displacement was plotted, and the maximum impact strength was calculated as the average value of the five samples.
[0302] [Measurement method of flexural storage modulus of continuous fiber reinforced resin molded body]
[0303] A continuous fiber reinforced resin molded body with a thickness of 2 mm was cut into a width of 5 mm and a length of 60 mm using a band saw along a direction of 0°, 90° or 45° (inclined direction) relative to the fiber direction, and a dynamic viscoelasticity measuring device (EPLEXOR-500N, GABO) was used to measure the deformation mode in a bending mode under a nitrogen atmosphere at a measuring temperature range of 25°C to 250°C, a heating rate of 3.0°C / min, and a vibration frequency of 8 Hz, and the maximum value was obtained as the bending storage modulus. In addition, the storage modulus at each temperature was obtained.
[0304] [Measurement method of tensile storage modulus and loss tangent of continuous fiber reinforced resin molded body]
[0305] The continuous fiber reinforced resin molded body with a thickness of 2 mm was cut into 5 mm wide and 60 mm long using a band saw along the direction of 0° and 90° relative to the fiber direction, and the deformation mode was measured in a tensile mode under the conditions of a measurement temperature range of 25°C to 250°C, a heating rate of 3.0°C / min, and a vibration frequency of 8Hz in a nitrogen atmosphere using a dynamic viscoelasticity measuring device (EPLEXOR-500N, GABO), and the storage modulus at each temperature was obtained. In addition, the loss tangent at each temperature was plotted, and the maximum value between 20°C and 200°C at this time was taken as the tensile loss tangent.
[0306] [Method for determining the melting point and cooling crystallization temperature of thermoplastic resin]
[0307] For a mixture of two or more thermoplastic resins or each resin, a DSC-60 manufactured by Shimadzu Corporation was used, with a sample amount of about 5 mg, an atmospheric gas flow rate of 30 mL / min, and a heating temperature of 10°C / min. Under these conditions, the mixture was heated from room temperature (25°C) to a temperature above the predicted melting point to melt the mixture, and then the molten polyamide resin was cooled at 10°C / min, and the temperature of the peak top of the exothermic peak observed at this time was taken as the crystallization temperature. The mixture was then heated again at a rate of 10°C / min to a temperature above the melting point, and the temperature of the peak top of the endothermic peak observed at this time was taken as the melting point.
[0308] [Measurement of the bonding strength between reinforcing fibers and each thermoplastic resin]
[0309] The continuous fiber reinforced resin molded body is cut into a thickness of 30 μm as a cross section orthogonal to the length direction of the reinforcing fiber, and is carefully ground in a manner that the continuous reinforcing fiber is not damaged. The ground sample is used to extrude the reinforcing fiber using a nanoindenter (iMicro, Nanomechenics, Inc.), thereby measuring the bonding strength between the reinforcing fiber and the thermoplastic resin. In the thermoplastic resin, the bonding strength between the resin (secondary resin) other than the resin (main resin) with the highest proportion of the resin area as a whole and the reinforcing fiber is greater than the bonding strength between the resin (main resin) with the highest proportion of the resin area as a whole and the reinforcing fiber is judged as "○", and the bonding strength between the secondary resin and the reinforcing fiber is weaker than the bonding strength between the main resin and the reinforcing fiber. It is judged as "×".
[0310] [Measurement of Wettability and Surface Tension]
[0311] One continuous reinforcing fiber is buried in a thermoplastic resin melted on a hot plate heated to 280°C, and a 1 mm continuous reinforcing fiber is pulled out at 1 mm / sec while being observed under a microscope. The evaluation is performed based on the length of the thermoplastic resin stretched by the continuous fiber. The wettability and surface tension of the case where the length of the resin (secondary resin) other than the resin (primary resin) with the highest proportion in the entire resin region among the thermoplastic resins stretched by the reinforcing fiber is greater than the length of the resin (primary resin) with the highest proportion in the entire resin region among the thermoplastic resins stretched by the reinforcing fiber is judged as "○", and the wettability and surface tension of the case where the length of the secondary resin stretched by the reinforcing fiber is weaker than the length of the main resin stretched by the reinforcing fiber is judged as "×".
[0312] [Measurement of melt viscosity of resin]
[0313] The measurement was performed using a double tube capillary rheometer (ROSAND PRECISION) at 280° C. with the shear rate changed to 100 / s, 200 / s, 400 / s, 1000 / s, 2000 / s, 4000 / s, and 8000 / s. The case where the melt viscosity of the mixture of two or more thermoplastic resins at a shear rate of 4000 / s was 4 / 5 to 5 / 4 times the viscosity of the resin with the highest proportion in the entire resin region among the two or more thermoplastic resins was judged as “○”, and the other cases were judged as “×”.
[0314] [Determination of water absorption of thermoplastic resin]
[0315] 0.3 g of the thermoplastic resin was weighed and measured under a nitrogen atmosphere using a Karl Fischer titrator (MKC610, manufactured by Kyoto Electronics Industry Co., Ltd.).
[0316] [Measurement of Flow Rate of Thermoplastic Resins During Heating and Pressing]
[0317] The flow rate was determined by measuring the weight of the resin leaking out during molding and dividing it by the weight of the original thermoplastic resin.
[0318] [Determination of the volume ratio of reinforcing fibers in continuous fiber-reinforced resin composite materials]
[0319] 2 g of continuous fiber reinforced resin composite material was cut out, placed in an electric furnace, and heated at 650°C for 3 hours to burn the resin. After cooling naturally to room temperature, the mass of the remaining glass fiber was measured to obtain the ratio of glass fiber to resin contained in the continuous fiber reinforced resin composite material. In addition, the obtained ratio was divided by the density to obtain the volume ratio (Vf) of the reinforcing fiber relative to the continuous fiber reinforced resin composite material.
[0320] [Measurement of the ratio of the sizing agent diffused into the thermoplastic resin]
[0321] 1g of continuous fiber reinforced resin composite material and 1g of continuous reinforcing fiber were immersed in 20mL of hexafluoroisopropanol (HFIP) respectively, and stirred for 5 hours using a stirring roller to dissolve the thermoplastic resin. The insoluble matter was washed twice with HFIP, further immersed in HFIP, and stirred for 5 hours with a stirring roller. The insoluble matter was washed twice with HFIP, vacuum dried, and measured using XPS (Versa probeII, ULVAC-PHI Co., Ltd.) under the conditions of excitation source mono.AlKα20kV×5mA 100W, analysis size 100μm×1.4mm, and photoelectron extraction angle.
[0322] [Determination of the amount of terminal functional groups]
[0323] 15 mg of the sample was dissolved in 1.5 mg of D2SO4 and the mixture was stirred at room temperature. 1 The amount of the terminal functional group was determined by H-NMR (JEOL-ECZ500).
[0324] [Acoustic Emission (AE) Method]
[0325] The acoustic emission method was measured as follows: a continuous fiber reinforced resin composite material cut to a length of 14 mm (7 times the thickness), a width of 10 mm, and a thickness of 2.0 mm was installed in an AE sensor (AE-900M) in an interlaminar shear test (JIS K7078) set at a span of 10 mm (5 times the thickness) and a test speed of 1 mm / min, thereby performing acoustic emission. The preamplifier was set to 34 dB, the threshold was set to 30 dB, and the filter was set to 95 kHz-960 kHz. The AE signal with an AE amplitude of less than 50 dB and a duration of the AE signal of less than 1000 μs was regarded as a signal corresponding to resin damage, the AE signal with an AE amplitude of 60 dB or more and a duration of the AE signal of 1000 μs or more was regarded as a signal corresponding to interlaminar delamination, and the AE signal with an AE amplitude of 50 dB or more and a duration of the AE signal of less than 1000 μs was regarded as a signal corresponding to glass fiber damage, and the analysis was performed.
[0326] [Determination of droplet formation coefficient]
[0327] The droplet generation coefficient was measured using a composite material interface property evaluation device (HM410, Toei Industry Co., Ltd.). The resin was placed in the heating furnace part of the device, and the temperature in the furnace was set to the melting point of the resin -40°C. The resin was applied to a single fiber of a reinforcing fiber placed in the device. When the resin was not melted and not attached to the reinforcing fiber, the temperature in the furnace was increased by 10°C each time until the resin melted, and the resin was applied to the reinforcing fiber. The molten resin was brought into contact with the reinforcing fiber 4 times. After the resin was attached, it was left to stand for 1 minute, and the number of droplets generated was counted and calculated by the following formula.
[0328] (droplet generation coefficient) = {(number of droplets generated) / 4} × 10
[0329] [Vibration fatigue test]
[0330] An ASTM-D1822 tensile impact dumbbell S-type test piece was prepared and tested using EHF-EB50kN-40L (RV) (Shimadzu Corporation) at a test temperature of 23°C, a frequency of 20 Hz, a sine wave waveform, a chuck spacing of 35 mm, and a minimum load of 10% of the load.
[0331] [Continuous reinforcing fiber]
[0332] [Glass fiber (A)]
[0333] A glass fiber with 0.45 mass % of a sizing agent attached thereto, a fineness of 11500 dtex, and a single-filament number of 2000 was produced. The winding form was DWR, and the average single-filament diameter was 17 μm.
[0334] The glass fiber sizing agent is prepared as follows: 0.5 mass% of γ-aminopropyltriethoxysilane (hereinafter referred to as aminosilane) KBE-903 (manufactured by Shin-Etsu Chemical Co., Ltd.), 1 mass% of carnauba wax, 2 mass% of polyurethane resin Y65-55 (manufactured by ADEKA Corporation), 40 mass% of maleic anhydride, 50 mass% of methyl acrylate and 10 mass% of methyl methacrylate are copolymerized, and the mixture is adjusted with deionized water so that the copolymer compound having a weight average molecular weight of 20,000 is 3 mass% and the copolymer compound aqueous solution is 3 mass%, thereby preparing the glass fiber sizing agent.
[0335] [Glass fiber B]
[0336] The same glass as the glass fiber (A) was produced except that the fineness was 2900 dtex, the number of filaments was 800, and the average filament diameter was 13 μm.
[0337] [Glass fiber C]
[0338] ER1200T-423 (Nippon Electric Glass Co., Ltd.)
[0339] [Thermoplastic resin]
[0340] Polyamide resin A: polyamide 66 (Leona 1300S (Asahi Kasei Corporation)), melting point 265°C, difference between melting peak temperature and cooling crystallization peak temperature (Tm-Tc) = 53°C, number of carboxyl terminal groups 70 μmol / g, number of amino terminal groups 32 μmol / g (Example 6-).
[0341] Polyamide resin B: polyamide 6 / 12 (Grilon C CF6S (EMS Chemie Japan Co., Ltd.)), melting point 130°C
[0342] Polyamide resin C: polyamide 66 (Leona 1402S (Asahi Kasei Corporation))
[0343] or polyamide 6 (Examples 4-, 5-) (Grilon BS2 natural (EMS Chemie Japan Co., Ltd.)), melting point 225°C
[0344] Polyamide 6I (Example 5-): Leona R16024 (Asahi Kasei Corporation) Glass transition temperature: 130°C Polyamide 6T / 6I (Example 5-): Prototype of Toyobo Co., Ltd.
[0345] Polyethylene (PE) (Example 5-): Suntec J240 (Asahi Kasei Corporation) Melting point: 125°C
[0346] [Polyamide film]
[0347] The thermoplastic resin A and / or B was molded using a T-die extruder (Soken Co., Ltd.) to obtain a film. The thickness of the film was 100 μm.
[0348] [Glass cloth, carbon fiber cloth]
[0349] The glass fibers were woven as warp and weft yarns using a rapier loom (weaving width 2 m) to produce glass cloth. The woven form of the obtained glass cloth was plain weave, the weaving density was 6.5 yarns / 25 mm, and the basis weight was 600 g / m 2 .
[0350] Glass cloth (Example 5-): WFR 350 100BS6 (Nittobo Co., Ltd.)
[0351] Carbon fiber cloth (Example 5-): A carbon fiber having a fineness of 8000 dtex and a filament number of 12000 and to which 2.8% by mass of polyvinyl pyrrolidone was attached was produced, and then woven (plain weave) using a rapier loom.
[0352] [Granular additives]
[0353] A masterbatch containing carbon black (Asahi Kasei Corporation) was used as a pelletized additive. The content of carbon black was 3 wt %.
[0354] [Manufacture of continuous fiber reinforced resin molded body]
[0355] As a molding machine, a hydraulic molding machine with a maximum clamping force of 50 tons (Shoji Co., Ltd.) was used. A mold with a concave structure for obtaining a flat plate-shaped continuous fiber-reinforced resin molded body (200 mm long, 100 mm wide, and 2 mm thick) was prepared.
[0356] The glass cloth and the polyamide film are cut into pieces in accordance with the shape of the mold, a predetermined number of pieces are stacked, and the pieces are placed in the mold.
[0357] The temperature in the molding machine was heated to 330°C, and then the mold was clamped at a clamping force of 5 MPa for compression molding. The molding time was set to 1 minute after the melting point of polyamide 66 reached 265°C. The mold was then rapidly cooled and opened to remove the molded body. The maximum temperature during molding was 275°C.
[0358] [Manufactured using a double belt press]
[0359] A double belt press (Process System Co., Ltd.) was used as a molding machine. Five sheets of the glass cloth and ten polyamide films were fed from a roll. The heating temperature of the device was set at 330°C and cooled by water. The press was applied at a pressure of 30 kN and conveyed at a speed of 0.2 m / min.
[0360] [Example 1-1]
[0361] Six sheets of glass cloth and seven sheets of polyamide resin A films were stacked and molded. The molding time was set to 1 minute after the melting point of polyamide 66 reached 265°C. After the mold was rapidly cooled, it was opened and the molded body was taken out. The maximum temperature during molding was 285°C.
[0362] [Example 1-2]
[0363] Six sheets of glass cloth and seven sheets of polyamide resin A films were stacked and molded. The temperature in the molding machine was set to 300°C, and the molding time was set to 15 minutes after the melting point of polyamide 66, 265°C, was reached. The mold was rapidly cooled and then opened to take out the molded body. The maximum temperature during molding was 300°C.
[0364] [Examples 1-3]
[0365] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 1-1 except that the molding was performed 30 seconds after the temperature reached 265°C. The maximum temperature during molding was 280°C.
[0366] [Examples 1-4]
[0367] A continuous fiber-reinforced resin molded product was obtained in the same manner as in Example 1-1 except that the polyamide film was obtained from a dry blend of the polyamide resin A and the polyamide resin B (A:B=8:1).
[0368] [Examples 1-5]
[0369] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 1-2 except that an epoxy resin was used instead of the film of the polyamide resin A.
[0370] The glass cloth was prepared using the glass fiber attached with 0.3% by mass of 3-glycidoxypropyltrimethoxysilane (KBM-402, Shin-Etsu Chemical Co., Ltd.) as a sizing agent, 1.5% by mass of epoxy resin emulsion, and 0.2% by mass of carnauba wax. Six sheets of the glass cloth were stacked and placed in a mold, and 16 g of bisphenol A type liquid epoxy resin (jER828, Mitsubishi Chemical Corporation) and 1.6 g of bisphenol A (4,4'-(propane-2,2-diyl) biphenol were added thereto. The temperature in the molding machine was set to 40°C, and compression molding was performed for 3 days at a clamping force of 5 MPa to obtain a continuous fiber reinforced resin molded body.
[0371] [Examples 1-6]
[0372] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 1-1 except that the number of glass cloth sheets was changed to 5 sheets and the number of polyamide resin A films was changed to 10 sheets.
[0373] [Comparative Example 1-1]
[0374] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 1-1 except that glass fibers to which no sizing agent was added were used.
[0375] [Comparative Example 1-2]
[0376] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 1-1 except that glass fibers to which 0.3% by mass of a silane coupling agent 3-glycidoxypropyltrimethoxysilane, 1.5% by mass of an epoxy resin emulsion, and 0.2% by mass of carnauba wax were attached were used.
[0377] [Comparative Examples 1-3]
[0378] The same evaluation as in Example 1-1 was performed on “Tepex dynalite 101” manufactured by Bond Laminate, in which glass cloth was impregnated with polyamide 66.
[0379] [Comparative Examples 1-6]
[0380] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 1-2 except that the molding was performed at a temperature in the molding machine set to 265°C. The maximum temperature during molding was 265°C.
[0381]
[0382] According to Table 1, the continuous fiber reinforced resin molded bodies of Examples 1-1 to 6 are continuous fiber reinforced resins in which the void fraction of the region of one tenth of the radius of one continuous reinforcing fiber from the end of one continuous reinforcing fiber is 10% or less and is 10% or more of the entire continuous fiber reinforced resin, and therefore exhibit very high tensile stress, bending stress, and bending modulus. These physical properties are significantly superior to those of the molded body obtained using the commercially available intermediate material in Comparative Example 1-3.
[0383] When continuous reinforcing fibers not coated with a sizing agent or coated with a sizing agent having poor compatibility with the resin were used as in Comparative Examples 1-1 and 2, the void ratio exceeded 10%, and the tensile stress, flexural stress, and flexural modulus decreased.
[0384] When the molding temperature is low as in Comparative Example 1-6, the void ratio is greater than 10%, and the tensile stress, flexural stress, and flexural modulus decrease.
[0385] [Example 2-1]
[0386] Six sheets of glass cloth and seven sheets of polyamide resin A films were stacked and molded. The molding time was set to 1 minute after the melting point of polyamide 66 reached 265°C. After the mold was rapidly cooled, it was opened and the molded body was taken out. The maximum temperature during molding was 285°C.
[0387] [Example 2-2]
[0388] Six sheets of glass cloth and seven sheets of polyamide resin A films were stacked and molded. The temperature in the molding machine was set to 300°C, and the molding time was set to 10 minutes after reaching the melting point of polyamide 66, 265°C. The mold was rapidly cooled and then opened to take out the molded body. The maximum temperature during molding was 300°C.
[0389] [Example 2-3]
[0390] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 2-1 except that the molding was performed 30 seconds after the temperature reached 265°C. The maximum temperature during molding was 280°C.
[0391] [Examples 2-4]
[0392] A continuous fiber-reinforced resin molded product was obtained in the same manner as in Example 2-1 except that the polyamide film was a film of polyamide resin B.
[0393] [Example 2-5]
[0394] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 2-1 except that the number of glass cloth sheets was changed to 5 sheets and the number of polyamide resin A films was changed to 10 sheets.
[0395] [Example 2-6]
[0396] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 2-2 except that the number of glass cloth sheets was changed to 5 sheets and the number of polyamide resin A films was changed to 10 sheets.
[0397] [Comparative Example 2-1]
[0398] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 2-1 except that glass fibers to which no sizing agent was added were used.
[0399] [Comparative Example 2-2]
[0400] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 2-6 except that glass fibers to which 0.3% by mass of a silane coupling agent 3-glycidoxypropyltrimethoxysilane, 1.5% by mass of an epoxy resin emulsion, and 0.2% by mass of carnauba wax were attached were used.
[0401] [Comparative Example 2-3]
[0402] The same evaluation as in Example 2-1 was performed on “Tepex dynalite 101” manufactured by Bond Laminate, in which glass cloth was impregnated with polyamide 66.
[0403]
[0404] According to Table 2, the continuous fiber reinforced resin molded bodies of Examples 2-1 to 6 have a loss tangent of 0.11 or less in the torsional mode, and thus exhibit very high impact absorption energy. These properties are significantly better than those of the molded body obtained using the commercial intermediate material in Comparative Example 2-3.
[0405] As shown in the comparative example, when the loss tangent is high, the impact absorption energy decreases.
[0406] [Example 3-1]
[0407] Six sheets of glass cloth and seven sheets of polyamide resin A films were stacked and molded. The molding time was set to 1 minute after the melting point of polyamide 66 reached 265°C. After the mold was rapidly cooled, it was opened and the molded body was taken out. The maximum temperature during molding was 285°C.
[0408] [Example 3-2]
[0409] Six sheets of glass cloth and seven sheets of polyamide resin A films were stacked and molded. The temperature in the molding machine was set to 300°C, and the molding time was set to 10 minutes after reaching the melting point of polyamide 66, 265°C. The mold was rapidly cooled and then opened to take out the molded body. The maximum temperature during molding was 300°C.
[0410] [Example 3-3]
[0411] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 3-1 except that the molding was performed 30 seconds after the temperature reached 265°C. The maximum temperature during molding was 280°C.
[0412] [Examples 3-4]
[0413] A continuous fiber-reinforced resin molded product was obtained in the same manner as in Example 3-1 except that the polyamide film was a film of polyamide resin B.
[0414] [Examples 3-5]
[0415] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 3-1 except that the number of glass cloth sheets was changed to 5 sheets and the number of polyamide resin A films was changed to 10 sheets.
[0416] [Examples 3-6]
[0417] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 3-2 except that the number of glass cloth sheets was changed to 5 sheets and the number of polyamide resin A films was changed to 10 sheets.
[0418] [Comparative Example 3-1]
[0419] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 3-1 except that glass fibers to which no sizing agent was added were used.
[0420] [Comparative Example 3-2]
[0421] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 3-6 except that glass fibers to which 0.3% by mass of a silane coupling agent 3-glycidoxypropyltrimethoxysilane, 1.5% by mass of an epoxy resin emulsion, and 0.2% by mass of carnauba wax were attached were used.
[0422] [Comparative Example 3-3]
[0423] The same evaluation as in Example 3-1 was performed on “Tepex dynalite 101” manufactured by Bond Laminate, in which glass cloth was impregnated with polyamide 66.
[0424]
[0425] According to Table 3, the continuous fiber reinforced resin molded bodies of Examples 3-1 to 6 have storage moduli in torsion mode of 3.4 GPa or more, and thus exhibit very high impact strength. These properties are significantly higher than those of the molded body obtained using a commercial intermediate material in Comparative Example 3-3.
[0426] When the storage modulus in the torsion mode is low like in the comparative example, the impact strength decreases.
[0427] [Example 4-1]
[0428] Five sheets of glass cloth and ten sheets of polyamide resin A films were overlapped and molded. The temperature in the molding machine was set to 300°C, and the molding time was set to 10 minutes after reaching the melting point of polyamide 66, 265°C. The mold was rapidly cooled and then opened to take out the molded body. The maximum temperature during molding was 300°C. The flexural storage modulus at this time was 31 GPa, the flexural storage modulus at 150°C was 24 GPa (retention rate 77%), the flexural storage modulus during oblique cutting was 20 GPa (retention rate 64%), the tensile storage modulus at 50°C was 25 GPa, the tensile loss tangent was 0.033, the temperature at which the tensile storage modulus and the flexural storage modulus reversed was 115°C, the value of {(tensile storage modulus at 30°C - flexural storage modulus)} / {(flexural storage modulus at 200°C - tensile storage modulus)} was 2.3, and the impact strength was 8.50 kN.
[0429] [Example 4-2]
[0430] Six sheets of glass cloth and seven sheets of polyamide resin A films were overlapped and molded. The temperature in the molding machine was set to 300°C, and the molding time was set to 10 minutes after reaching the melting point of polyamide 66, 265°C. The mold was quenched and then opened to take out the molded body. The maximum temperature during molding was 300°C. The flexural storage modulus at this time was 37 GPa, and the impact strength was 9.25 kN.
[0431] [Example 4-3]
[0432] A continuous fiber reinforced resin molded body was obtained in the same manner as in Example 4-2 except that the molding was performed 30 seconds after reaching 265° C. The maximum temperature during molding was 280° C. The flexural storage modulus at this time was 28 GPa, and the impact strength was 8.81 kN.
[0433] [Example 4-4]
[0434] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 4-2 except that the polyamide film was a film of polyamide resin B. The flexural storage modulus at this time was 33 GPa, and the impact strength was 9.05 kN.
[0435] [Examples 4-5]
[0436] A continuous fiber reinforced resin molded body was obtained in the same manner as in Example 4-1 except that the molding was performed 1 minute after the temperature reached 265° C. The maximum temperature during molding was 285° C. The flexural storage modulus at this time was 31 GPa, and the impact strength was 8.50 kN.
[0437] [Examples 4-6]
[0438] Six sheets of glass cloth and seven sheets of polyamide resin A films were overlapped and molded. The molding time was set to 1 minute after the melting point of polyamide 66 reached 265°C. The mold was quenched and then opened to take out the molded body. The maximum temperature during molding was 285°C. The flexural storage modulus at this time was 36 GPa and the impact strength was 9.10 kN.
[0439] [Comparative Example 4-1]
[0440] A continuous fiber-reinforced resin molded body was obtained in the same manner as in Example 6 except that glass fibers without a sizing agent were used. The flexural storage modulus was 15 GPa, and the impact strength was 3.20 kN.
[0441] [Comparative Example 4-2]
[0442] A continuous fiber reinforced resin molded body was obtained in the same manner as in Example 4-1 except that glass fibers to which 0.3% by mass of 3-glycidoxypropyltrimethoxysilane as a sizing agent, 1.5% by mass of epoxy resin emulsion, and 0.2% by mass of carnauba wax were attached were used. The flexural storage modulus was 20 GPa and the impact strength was 5.21 kN.
[0443] [Comparative Example 4-3]
[0444] The same evaluation as in Example 4-1 was performed on "Tepex dynalite 101" manufactured by Bond Laminate, in which polyamide 66 was impregnated in glass cloth. The flexural storage modulus at this time was 20.8 GPa, the flexural storage modulus at 150°C was 15.7 GPa (retention rate 75%), the flexural storage modulus during oblique cutting was 11.9 GPa (retention rate 57%), the tensile storage modulus at 50°C was 21 GPa, the tensile loss tangent was 0.038, the temperature at which the tensile storage modulus and the flexural storage modulus reversed was 90°C, the value of {(tensile storage modulus at 30°C - flexural storage modulus)} / {(flexural storage modulus at 200°C - tensile storage modulus)} was 0.57, and the impact strength was 5.32 kN.
[0445] The continuous fiber reinforced resin molded bodies of Examples 4-1 to 6 had a flexural storage modulus of 22 GPa or more, and thus showed very high impact strength. These physical properties were significantly better than those of the molded body obtained using a commercial intermediate material in Comparative Example 4-3.
[0446] When the flexural storage modulus is low as in the comparative example, the impact strength is reduced.
[0447] [Example 5-1]
[0448] PA66 and PA6 / 12 were dry-mixed at a weight ratio of 8:1 and used to manufacture a thermoplastic resin film. The thickness of the film was 100 μm. 11 sheets of the film were alternately layered with 10 sheets of glass cloth to form a film. In the resin region other than the extreme interface region with the glass fiber, PA6 / 12 was uniformly dispersed in PA66.
[0449] [Example 5-2]
[0450] A continuous fiber reinforced resin molded body was produced in the same manner as in Example 5-1 except that PA6 was used instead of PA6 / 12. PA6 was uniformly dispersed in PA66 in the resin region other than the interface region with the glass fiber.
[0451] [Example 5-3]
[0452] A continuous fiber reinforced resin molded body was produced in the same manner as in Example 5-1 except that PE was used instead of PA6 / 12. PE was uniformly dispersed in PA66 in the resin region other than the polar interface region with the glass fiber.
[0453] [Example 5-4]
[0454] A continuous fiber reinforced resin molded body was produced in the same manner as in Example 5-1 except that PA6I was used instead of PA6 / 12. PA6I was uniformly dispersed in PA66 in the resin region other than the polar interface region with the glass fiber.
[0455] [Example 5-5]
[0456] A continuous fiber reinforced resin molded body was produced in the same manner as in Example 5-1 except that PA66 and PA6 / 12 were dry-blended at a weight ratio of 5:4. PA6 / 12 was uniformly dispersed in PA66 in the resin region other than the extreme interface region with the glass fiber.
[0457] [Examples 5-6]
[0458] A continuous fiber reinforced resin molded body was produced in the same manner as in Example 5-1 except that PA66 and PA6 / 12 were pre-mixed at a feed ratio (weight ratio) of 8:1 using a twin-screw extruder (TEM26SS, Toshiba Machine) and used to produce a thermoplastic resin film. PA6 / 12 was uniformly dispersed in PA66 in the resin region other than the interface region with the glass fiber.
[0459] [Examples 5-7]
[0460] A continuous fiber reinforced resin molded body was produced in the same manner as in Example 5-1 except that carbon fiber cloth was used instead of glass cloth. In the resin region other than the interface region with the glass fiber, PA6 / 12 was uniformly dispersed in PA66.
[0461] [Comparative Example 5-1]
[0462] A continuous fiber-reinforced resin molded body was produced in the same manner as in Example 5-1 except that only PA66 was used to produce the film.
[0463] [Comparative Example 5-2]
[0464] A continuous fiber reinforced resin molded body was produced in the same manner as in Example 5-1 except that PA6T / 6I was used instead of PA6 / 12. PA6T / 6I was uniformly dispersed in PA66 in the resin region other than the polar interface region with the glass fiber and in the polar interface region.
[0465] [Comparative Example 5-3]
[0466] The glass cloth was cut into 19.5 cm × 9.5 cm, immersed in a solution of amide emulsion (Sepolsion PA200, Sumitomo Seika Co., Ltd.) adjusted to 30% by mass with pure water, and then dried in a hot air circulation dryer at 80°C for 1 hour to prepare a composite material. In the obtained composite material, the solid content of the polyamide emulsion, i.e., the amount of PA6 / 12 attached to the glass cloth was 6% by mass. It was then laminated with a PA66 film to produce a continuous fiber reinforced resin molded body in the same manner as in Example 5-1. In this example, PA6 / 12 was not uniformly dispersed in PA66, but only existed in the polar interface region.
[0467] [Comparative Example 5-4]
[0468] A continuous fiber reinforced resin molded body was produced in the same manner as in Example 5-1 except that PA66 and PA6 / 12 were dry-blended at a weight ratio of 1:8. PA66 was uniformly dispersed in PA6 / 12 in the resin region other than the extreme interface region with the glass fiber.
[0469] The results of Examples 5-1 to 7 and Comparative Examples 5-1 to 4 are listed in Table 4 below.
[0470]
[0471] According to Table 4, as shown in Examples 5-1 to 7, in the continuous fiber reinforced resin molded body of the present embodiment, at the extreme interface between one of the continuous reinforcing fibers and the thermoplastic resin in the cross section perpendicular to the longitudinal direction of the continuous reinforcing fibers, in the peripheral outer region which is one tenth of the radius of one of the two or more continuous reinforcing fibers from the peripheral portion of the continuous reinforcing fibers, the proportion of the resin (secondary resin) other than the resin (main resin) with the highest proportion in the entire resin region among the two or more thermoplastic resins is higher than the proportion of the main resin, and in the resin region outside the peripheral outer region, each secondary resin other than the resin (main resin) with the highest proportion in the entire resin region among the two or more thermoplastic resins is uniformly dispersed or mixed, so that high tensile stress, bending stress, bending modulus, and tensile stress at high temperature are exhibited. On the other hand, as shown in Comparative Example 5-1, when the thermoplastic resin is one, the bonding between the reinforcing fiber and the thermoplastic resin is insufficient, and the tensile stress, bending stress, bending modulus, and tensile stress at high temperature are reduced. In addition, as shown in Comparative Examples 5-2 and 5-4, even if there are two or more thermoplastic resins, in the peripheral outer region of one tenth of the radius of one of the two or more continuous reinforcing fibers from the peripheral portion of the continuous reinforcing fibers, when the proportion of the resin (main resin) with the highest proportion in the entire resin region among the two or more thermoplastic resins is higher than the proportion of the secondary resin, the bonding between the reinforcing fibers and the thermoplastic resin is insufficient, and the tensile stress, bending stress, bending modulus, and tensile stress at high temperature are reduced. In addition, as shown in Comparative Example 5-3, in the peripheral outer region of one tenth of the radius of one of the two or more continuous reinforcing fibers from the peripheral portion of the continuous reinforcing fibers, even if there is a secondary resin other than the resin (main resin) with the highest proportion in the entire resin region among the two or more thermoplastic resins, the secondary resin is not uniformly dispersed or mixed in the resin region outside the peripheral outer region, so the tensile stress at high temperature is reduced.
[0472] [Example 6-1]
[0473] Five sheets of glass cloth and ten sheets of polyamide resin film were overlapped and molded using a double belt press. The water absorption of the polyamide resin was 0.2 wt %. A photograph of the polar interface region of the obtained molded product is shown in Figure 3 .
[0474] [Example 6-2]
[0475] Five sheets of glass cloth and ten sheets of polyamide resin film were overlapped and molded using a mold. The molding time was set to 1 minute after the melting point of polyamide 66 reached 265°C. The mold was quenched and then opened to take out the molded body. The maximum temperature during molding was 285°C. The water absorption of the polyamide resin was 0.2wt%.
[0476] [Example 6-3]
[0477] A continuous fiber reinforced resin composite material was obtained in the same manner as in Example 6-1 except that the polyamide resin film was dried in a vacuum dryer before molding. The water absorption of the polyamide resin was 0.01 wt%.
[0478] [Example 6-4]
[0479] When forming a polyamide film, the polyamide resin and the carbon black masterbatch were dry-mixed and formed to form a polyamide resin film. A continuous fiber reinforced resin composite material was obtained in the same manner as in Example 1. The water absorption of the polyamide resin was 0.2 wt %. The content of carbon black was 90 ppm. It should be noted that in the examples and comparative examples other than Example 6-4, carbon black as a granular additive was not contained.
[0480] [Example 6-5]
[0481] A continuous fiber-reinforced resin composite material was obtained in the same manner as in Example 6-1 except that polyamide 66 having a carboxyl terminal group content of 50 μmol / g and a carboxyl terminal group content of 30 μmol / g were used. The water absorption of the polyamide resin was 0.2 wt %.
[0482] [Example 6-6]
[0483] A continuous fiber-reinforced resin composite material was obtained in the same manner as in Example 6-1 except that polyamide 66 having a carboxyl terminal group content of 70 μmol / g and an amino terminal group content of 50 μmol / g was used. The water absorption of the polyamide resin was 0.2 wt %.
[0484] [Examples 6-7]
[0485] A continuous fiber reinforced resin composite material was obtained in the same manner as in Example 6-1 except that polyamide 66 and 0.05 wt% of sodium hypophosphite as a catalyst for promoting the reaction between the silane coupling agent and the carboxyl terminal group were kneaded using a twin-screw kneader and the kneaded product was used as a thermoplastic resin. The water absorption of the polyamide resin was 0.2 wt%.
[0486] [Examples 6-8]
[0487] A continuous fiber reinforced resin composite material was obtained in the same manner as in Example 6-1 except that 0.05 wt% of sodium hypophosphite was added to the sizing agent of the glass fiber. The water absorption of the polyamide resin was 0.2 wt%.
[0488] [Examples 6-9]
[0489] A continuous fiber-reinforced resin composite material was obtained in the same manner as in Example 6-2 except that a mold with an opening in the longitudinal direction was used as the mold. The water absorption of the polyamide resin was 0.2 wt %.
[0490] [Comparative Example 6-1]
[0491] A continuous fiber-reinforced resin composite material was obtained in the same manner as in Example 1 except that glass fibers without a sizing agent were used.
[0492] [Comparative Example 6-2]
[0493] A continuous fiber reinforced resin composite material was obtained in the same manner as in Example 6-1 except that glass fibers to which 0.3% by mass of 3-glycidoxypropyltrimethoxysilane as a sizing agent, 1.5% by mass of epoxy resin emulsion, and 0.2% by mass of carnauba wax were attached were used. A photograph of the polar interface region of the obtained molded article is shown in Figure 4 .
[0494]
[0495] According to Table 5, the continuous fiber reinforced resin composite materials of Examples 6-1 to 6-9 exhibited very high tensile stress, flexural stress, and flexural modulus because the coupling agent was reactive with the terminal functional group contained in the thermoplastic resin.
[0496] When the water absorption rate of the thermoplastic resin is low as in Example 6-3, degradation of physical properties is observed.
[0497] When the content of the particulate additive is high as in Example 6-4, a decrease in physical properties is observed.
[0498] When the amount of carboxyl terminal groups of the polyamide resin is small as in Example 6-5, deterioration of physical properties is observed.
[0499] When the amount of amino terminal groups in the polyamide resin is large as in Example 6-6, deterioration in physical properties is observed.
[0500] When the flow rate of the thermoplastic resin during pressing is high as in Example 6-9, the coupling agent and the terminal functional group contained in the thermoplastic resin fail to react sufficiently, and degradation of physical properties is observed.
[0501] In Comparative Example 6-1 using continuous reinforcing fibers not coated with a sizing agent and Comparative Example 6-2 using continuous reinforcing fibers coated with a sizing agent including a coupling agent substantially unreactive with the terminal groups of the resin, the tensile stress, flexural stress, and flexural modulus decreased.
[0502] [Example 7-1]
[0503] Five sheets of glass cloth using glass fiber A and ten sheets of polyamide resin A films were stacked and pressed using a mold. The molding time was set to 1 minute after reaching the melting point of polyamide 66, 265°C. The mold was quenched and then opened to take out the molded body. The maximum temperature during molding was 285°C. The A / E method was performed on the molded product to measure the breaking strength caused by interlayer peeling.
[0504] [Example 7-2]
[0505] A continuous fiber-reinforced resin composite material was obtained in the same manner as in Example 7-1 except that the glass fiber C was used as the continuous reinforcing fiber.
[0506] [Example 7-3]
[0507] A continuous fiber-reinforced resin composite material was obtained in the same manner as in Example 7-2 except that the molding was performed using a double belt apparatus.
[0508] [Comparative Example 7-1]
[0509] The same evaluation as in Example 7-1 was performed on “Tepex dynalite 101” manufactured by Bond Laminate, in which glass cloth was impregnated with polyamide 66.
[0510]
[0511] According to Table 6, the continuous fiber reinforced resin composite materials of Examples 7-1 to 7-3 have higher fracture strength due to interlaminar delamination than those of Comparative Example 7-1, and thus exhibit significantly higher tensile stress, flexural stress, flexural modulus, and impact properties.
[0512] [Example 8-1]
[0513] Five sheets of glass cloth using glass fiber A and ten sheets of film of polyamide resin A were overlapped and pressed using a mold. The molding time was set to 1 minute after reaching the melting point of polyamide 66, 265°C. The mold was quenched and then opened to take out the molded body. The maximum temperature during molding was 285°C. The droplet generation coefficient of glass fiber A and polyamide resin A was 25.
[0514] [Example 8-2]
[0515] A continuous fiber reinforced resin composite material was obtained in the same manner as in Example 8-1 except that the glass fiber C was used. The droplet generation coefficient of the glass fiber C and the polyamide resin A was 27.
[0516] [Comparative Example 8-1]
[0517] A continuous fiber-reinforced resin composite material was obtained in the same manner as in Example 8-1 except that a film of polyamide resin C was used as the polyamide resin. The droplet generation coefficient of glass fiber A and polyamide resin C was 3.
[0518] [Comparative Example 8-2]
[0519] A continuous fiber-reinforced resin composite material was obtained in the same manner as in Comparative Example 8-1 except that the glass fiber was glass fiber C. The droplet generation coefficient between the glass fiber C and the polyamide resin C was 3.
[0520]
[0521] According to Table 7, the continuous fiber reinforced resin composite materials of Examples 8-1 and 8-2 have higher droplet generation coefficients than those of Comparative Examples 8-1 and 8-2, and thus exhibit significantly higher tensile stress, bending stress, bending modulus, impact properties, and long-term properties.
[0522] [Example 9]
[0523] Production Fig.12 Smartphone housing of the shape shown. One sheet of glass cloth using glass fiber C is sandwiched between films of polyamide resin A and press-molded.
[0524] The obtained molded product has a thickness of 0.4 mm, dimensions of 135 mm in the length direction, 65 mm in the width direction, and a side wall height of 5 mm. The tensile strength in the length direction is 550 MPa, the bending modulus is 35 MPa, the tensile strength in the width direction is 530 MPa, and the bending modulus is 33 MPa. In addition, the electric field shielding properties of the planar portion of the molded product were measured using the KEC method. The results showed that the electric field shielding properties were 0 dB at a frequency band of 1 GHz, indicating that the product has excellent radio wave transmittance.
[0525] Regarding the appearance of the molded product, it is a molded product with less fiber disorder and good appearance.
[0526] The tensile strength was measured in accordance with JIS K7161. In addition, the flexural modulus was measured in accordance with JIS K7171. In addition, regarding the electric field shielding properties, a molded product cut into a square of 5 cm × 5 cm was attached to an aluminum sample fixing fixture using a conductive tape, and electrolysis (KEC method) was performed using an "Anritsu" electric wave shielding properties tester MA8602C, and the electric field shielding properties at 1 GHz were measured using an "Anritsu" spectrum analyzer MS2661C.
[0527] [Example 10]
[0528] The glass fiber C was chopped into 3 mm and mixed with the polyamide resin A using a co-rotating twin-screw compounding extruder HK-25D (41D) φ25 mm, L / D=41 (Parker Corporation) and a metering device (gravimetric twin-screw feeder K-CL-24-KT20 (K-Tron)) at a screw speed of 175 rpm and a feed rate of 5 kg / h to obtain pellets. The obtained pellets were used to produce JISK 7139 multi-purpose test piece A1 type, t4 mm molded products using an electric injection molding machine (NEX140 (Nissei Plastic Industry Co., Ltd.), clamping force 140 tf / screw diameter φ40 / full-thread screw) under the conditions of JISK 7152-1. The observation photograph of the polar interface at this time is shown in Fig.10 .
[0529] [Comparative Example 10]
[0530] A molded article was produced in the same manner as in Example 10 except that the polyamide resin was changed to polyamide resin C. The observation photograph of the polar interface at this time is shown in FIG. Fig.11 .
[0531] like Fig.10 , 11 As shown, when the droplet generation coefficient is 10 or more and the compatibility between the glass fiber and the resin is good, a good polar interface can be formed.
[0532] Industrial Applicability
[0533] The continuous fiber reinforced resin molded body of the present embodiment can be used in industry as a reinforcing material for materials requiring high mechanical properties such as structural parts of various machines or automobiles, and as a composite molded body material with a thermoplastic resin composition. In addition, by using the method for manufacturing a continuous fiber reinforced resin composite material of the present invention, a continuous fiber reinforced resin composite material having high adhesion and affinity at the interface between the continuous reinforcing fiber and the thermoplastic resin, voids existing in the interface, and sufficient strength can be obtained.
[0534] Explanation of symbols
[0535] r is the radius of the continuous reinforcing fiber with a roughly circular cross-section
[0536] 1 Synthetic resin
[0537] 2 Continuous reinforcement fibers
[0538] 3. Gap
[0539] 4 Continuous reinforcing fiber bundles
[0540] 5 At the extreme interface between one continuous reinforcing fiber and the thermoplastic resin in a cross section perpendicular to the longitudinal direction of the continuous reinforcing fiber, in an outer region of the periphery of the continuous reinforcing fiber that is one tenth of the radius of the continuous reinforcing fiber
[0541] 6 Continuous reinforcement fiber
[0542] 7 A resin (secondary resin) other than the resin (primary resin) that has the highest proportion in the entire resin region among two or more thermoplastic resins
[0543] 8 The resin (main resin) that occupies the largest proportion in the entire resin region among two or more thermoplastic resins.
Claims
1. A continuous fiber reinforced resin molded body comprising continuous reinforcing fibers having a substantially circular cross section and two or more thermoplastic resins, characterized in that: At the extreme interface between one of the continuous reinforcing fibers and the thermoplastic resin in a cross section perpendicular to the longitudinal direction of the continuous reinforcing fibers, in a peripheral outer region that is one-tenth of the radius of one of the continuous reinforcing fibers away from the peripheral portion of the continuous reinforcing fibers, the proportion of the resin other than the resin with the highest proportion in the entire resin region among the two or more thermoplastic resins is higher than the proportion of the resin with the highest proportion in the entire resin region, and in the resin region outside the peripheral outer region, the resin other than the resin with the highest proportion in the entire resin region among the two or more thermoplastic resins is uniformly dispersed or mixed, The difference in surface tension between at least one resin other than the resin having the highest proportion in the entire resin region among the two or more thermoplastic resins and the continuous reinforcing fibers is smaller than the difference in surface tension between the resin having the highest proportion in the entire resin region and the continuous reinforcing fibers, The thermoplastic resin is a polyamide-based resin, and the difference between the melting points of the resin with the highest melting point and the resin with the lowest melting point among the two or more thermoplastic resins is 95° C. or more.
2. The continuous fiber reinforced resin molded body according to claim 1, wherein: The two or more thermoplastic resins have a sea-island structure.
3. The continuous fiber reinforced resin molded body according to claim 1 or 2, wherein: Among the two or more thermoplastic resins, the difference between the melting points of the resin having the highest melting point and the resin having the lowest melting point is 100° C. or more.
4. The continuous fiber reinforced resin molded body according to claim 1 or 2, wherein: The melting point of the mixture of the two or more thermoplastic resins is substantially the same as the melting point of the resin having the highest proportion in the entire resin region among the two or more thermoplastic resins.
5. The continuous fiber reinforced resin molded body according to claim 1 or 2, wherein: The difference between the heating melting peak temperature and the cooling crystallization peak temperature of the mixture of the two or more thermoplastic resins is smaller than the difference between the heating melting peak temperature and the cooling crystallization peak temperature of the resin with the highest proportion in the entire resin region among the two or more thermoplastic resins.
6. The continuous fiber reinforced resin molded body according to claim 1 or 2, wherein: The bonding force between at least one resin other than the resin having the highest proportion in the entire resin region among the two or more thermoplastic resins and the continuous reinforcing fibers is greater than the bonding force between the resin having the highest proportion in the entire resin region and the continuous reinforcing fibers.
7. The continuous fiber reinforced resin molded body according to claim 1 or 2, wherein: Among the two or more thermoplastic resins, at least one resin other than the resin with the highest proportion in the entire resin region has higher wettability to the continuous reinforcing fibers than the resin with the highest proportion in the entire resin region.
Citation Information
Patent Citations
Production of chinmi (dried and seasoned fish meat for drinking "sake" and other alcoholic beverage)
JP1983078544A
Inspecting method of optical fiber
JP1984087335A
Molding material and its manufacture
JP1998138379A
Glass fiber and glass fiber reinforced resin using the same as reinforcing material
JP2003238213A
Molding material, preform and fiber-reinforced resin
JP2009019202A